Packaging films and bags

By designing the structure of polypropylene-based sublayer, oxide deposit layer and gas Barrier coating in the gas Barrier film, the problem that the oxygen barrier performance and interlayer bonding strength of the traditional gas Barrier film are difficult to meet simultaneously after heating and disinfection treatment, and excellent performance under high temperature conditions is achieved.

JP7658492B2Active Publication Date: 2025-04-08TOPPAN HOLDINGS INC
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
JP2024061722
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-05-12
Filing Date
2024-04-05
Publication Date
2025-04-08
Estimated Expiration
2043-05-11

AI Technical Summary

Technical Problem

Traditionally, polypropylene-based gas Barrier membranes are difficult to achieve excellent oxygen barrier properties and interlayer bonding strength at the same time after heating and disinfection.

Method used

The gas Barrier film structure is adopted which consists of a polypropylene-based sublayer, an oxide depositing layer and a gas Barrier coating, wherein the sublayer comprises a first cortical layer with a hardness of 0.02-0.15 GPa and a core layer with a hardness of 0.07 GPa or higher. The oxide depositing layer is composed of aluminum oxide or silicon oxide, and the gas Barrier coating is a cured product of a water-soluble polymer hydroxide and its metal alcohol oxide or silane coupling agent.

Benefits of technology

After heating and disinfection, the gas Barrier film maintains excellent oxygen barrier properties and interlayer bonding strength, and is suitable for the preparation of packaging films and packaging bags.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658492000015
    Figure 0007658492000015
  • Figure 0007658492000016
    Figure 0007658492000016
  • Figure 0007658492000017
    Figure 0007658492000017
Patent Text Reader

Abstract

To provide a gas barrier film which can achieve both good oxygen barrier property and interlayer adhesion after heating sterilization treatment while having a polypropylene-based base material.SOLUTION: A gas barrier film includes a base material layer containing a polypropylene-based resin, a vapor-deposited layer containing an inorganic oxide and a gas barrier coating layer in this order, wherein the base material layer includes a first skin layer and a core layer, the vapor-deposited layer is formed on the first skin layer side, hardness of the first skin layer, which is measured by a nanoindentation method, is 0.02 to 0.15 GPa, and hardness of the core layer which is measured thereby is 0.07 GPa or more, and the hardness of the core layer is greater than the hardness of the first skin layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a gas barrier film, a packaging film, and a packaging bag. [Background technology]

[0002] Gas barrier films are widely used as packaging materials for foods and medicines that undergo heat sterilization treatment such as boiling and retort treatment. When packaging contents such as foods and medicines, it is important to reduce the oxygen permeability in order to prevent the contents from deteriorating or spoiling and to maintain their quality. For this reason, gas barrier films suitable for such applications have traditionally been made of polyethylene terephthalate film substrates that are heat resistant and have a low oxygen permeability.

[0003] Meanwhile, in relation to packaging materials with gas barrier films, in order to improve recyclability in response to growing awareness of environmental issues, studies are being conducted on packaging materials using a single material, so-called mono-material packaging materials.Since polyolefin films such as polypropylene are generally used in packaging materials, in order to produce mono-material packaging materials, it is required to use a polyolefin film as the base material of the gas barrier film as well.

[0004] Polypropylene films as polyolefin films are excellent in transparency, mechanical strength, heat resistance, etc. Therefore, the use of polypropylene films as the base material of gas barrier films has been considered. For example, Patent Document 1 below proposes a method of blending an ethylene-α-olefin copolymer into a polypropylene film, and Patent Documents 2 and 3 propose methods of laminating different polypropylene films. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 63-291929 [Patent Document 2] Japanese Patent Application Publication No. 63-290743 [Patent Document 3] Patent No. 2969657 Summary of the Invention [Problem to be solved by the invention]

[0006] However, with conventional gas barrier films using polypropylene films, it is difficult to achieve both good oxygen barrier properties and good interlayer adhesion after heat sterilization treatment.

[0007] An object of one aspect of the present disclosure is to provide a gas barrier film that has a polypropylene-based base material and is capable of achieving both good oxygen barrier properties and interlayer adhesion after heat sterilization treatment. Another object of one aspect of the present disclosure is to provide a packaging film and a packaging bag using the gas barrier film. [Means for solving the problem]

[0008] One aspect of the present disclosure provides a gas barrier film comprising a substrate layer containing a polypropylene-based resin, a vapor deposition layer containing an inorganic oxide, and a gas barrier coating layer, in this order, wherein the substrate layer comprises a first skin layer and a core layer, the vapor deposition layer is formed on the first skin layer side, and the hardness of the first skin layer is 0.02 to 0.15 GPa and the hardness of the core layer is 0.07 GPa or more, as measured by a nanoindentation method, and the hardness of the core layer is greater than the hardness of the first skin layer.

[0009] Such a gas barrier film has a polypropylene-based base material and yet is capable of achieving both good oxygen barrier properties and interlayer adhesion after heat sterilization treatment.

[0010] In one embodiment, the first skin layer may comprise a propylene-α-olefin copolymer.

[0011] In one embodiment, the ratio of the thickness of the first skin layer to the thickness of the core layer may be from 1 / 100 to 1 / 5.

[0012] In one embodiment, the first skin layer may have a composite elastic modulus of 1.2 to 2.5 GPa, and the core layer may have a composite elastic modulus of 2.0 GPa or more, as measured by nanoindentation.

[0013] In one embodiment, the inorganic oxide may include at least one of aluminum oxide and silicon oxide.

[0014] In one embodiment, the gas barrier coating layer may be made of a cured product of a composition containing a water-soluble polymer having a hydroxyl group and at least one selected from the group consisting of a metal alkoxide, a silane coupling agent, and a hydrolyzate thereof.

[0015] In one embodiment, the gas barrier film may further include an anchor coat layer between the substrate layer and the deposition layer.

[0016] In one embodiment, the substrate layer may comprise, in order, a first skin layer, a core layer and a second skin layer.

[0017] In one embodiment, the second skin layer may comprise a propylene-α-olefin copolymer.

[0018] In one embodiment, the hardness of the second skin layer may be 0.02 to 0.15 GPa as measured by nanoindentation.

[0019] In one embodiment, the thickness of the deposited layer may be 5 nm or more and 80 nm or less.

[0020] Another aspect of the present disclosure provides a packaging film comprising the above-mentioned gas barrier film, a sealant layer overlying the gas barrier coating layer, and an adhesive layer bonding the gas barrier coating layer and the sealant layer, wherein after the packaging film is subjected to a retort treatment, the hardness of the adhesive layer measured by a nanoindentation method is 0.1 MPa or more and less than 0.9 MPa.

[0021] In one embodiment, the hardness of the adhesive layer measured by nanoindentation before the retort treatment may be 1.0 MPa or more.

[0022] In one embodiment, the thickness of the adhesive layer may be from 0.5 μm to 10 μm.

[0023] In one embodiment, each of the base layer and the sealant layer is a polyolefin film, and the total mass ratio of the polyolefin in the packaging film may be 90 mass % or more.

[0024] In one embodiment, the substrate layer may be an oriented polypropylene film and the sealant layer may be an unoriented polypropylene film.

[0025] In one aspect, the packaging film further comprises an outermost layer overlying the substrate layer and a second adhesive layer adhering the outermost layer and the substrate layer, the adhesive layer adhering the substrate layer and the sealant layer, and the second adhesive layer adhering the substrate layer and the outermost layer.

[0026] In one embodiment, after exposing the outermost layer to 120°C for 15 minutes, the thermal shrinkage rate in the MD direction of the outermost layer calculated by the following formula (1) may be 1% or more, and after performing retort treatment on the packaging film, the hardness of the second adhesive layer measured by the nanoindentation method may be 0.1 MPa or more and less than 0.9 MPa. Thermal shrinkage rate in MD direction (%) = (MD length before heating - MD length after heating) / MD length before heating × 100 ... (1)

[0027] One aspect of the present disclosure provides a packaging bag which is a product made from the above packaging film. Effect of the Invention

[0028] According to one aspect of the present disclosure, it is possible to provide a gas barrier film that has a polypropylene-based base material and is capable of achieving both good oxygen barrier properties and interlayer adhesion after heat sterilization treatment. Also, according to one aspect of the present disclosure, it is possible to provide a packaging film and a packaging bag using the gas barrier film. [Brief description of the drawings]

[0029] [Figure 1] 1 is a schematic cross-sectional view showing a gas barrier film according to a first embodiment. [Diagram 2] FIG. 4 is a schematic cross-sectional view showing a gas barrier film according to a modified example of the first embodiment. [Diagram 3] FIG. 1 is a schematic cross-sectional view showing a packaging film according to a first embodiment. [Figure 4] FIG. 4 is a schematic cross-sectional view showing a packaging film according to a modified example of the first embodiment. [Diagram 5] 5A and 5B are diagrams showing a laminate according to a second embodiment, in which (a) of FIG. 5 is a schematic plan view of the laminate according to the second embodiment, and (b) of FIG. 5 is a schematic cross-sectional view of the laminate according to the second embodiment. [Figure 6] 11 is a schematic front view of an example of a packaging bag according to a second embodiment. FIG. [Figure 7] FIG. 11 is a schematic cross-sectional view showing a laminate according to a modified example of the second embodiment. [Figure 8] FIG. 2 is a schematic diagram showing a method for measuring the thermal shrinkage rate during heating in an oven. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the drawings where necessary. However, the present disclosure is not limited to the following embodiments.

[0031] [First embodiment] <Gas barrier film> Fig. 1 is a schematic cross-sectional view showing a gas barrier film according to a first embodiment. As shown in Fig. 1, a gas barrier film 10a includes a base layer 1, a deposition layer 2, and a gas barrier coating layer 3, in this order. The base layer 1 includes a first skin layer 11 and a core layer 12, and the deposition layer 2 is formed on the first skin layer 11 side. In other words, the deposition layer 2 is formed on the first skin layer 11.

[0032] Fig. 2 is a schematic cross-sectional view showing a gas barrier film according to a modified example of the first embodiment. As shown in Fig. 2, the gas barrier film 10b includes a base layer 1, a deposition layer 2, and a gas barrier coating layer 3, in this order. The base layer 1 includes a first skin layer 11, a core layer 12, and a second skin layer 13, and the deposition layer 2 is formed on the first skin layer 11 side. In other words, the deposition layer 2 is formed on the first skin layer 11.

[0033] [Base material layer] The substrate layer is a film (base film) that serves as a support, and contains a polypropylene-based resin. Examples of the polypropylene-based resin include homopolypropylene and propylene copolymer. Examples of the propylene copolymer include polypropylene-based copolymers such as propylene-ethylene random copolymers, propylene-ethylene block copolymers, and propylene-α-olefin copolymers.

[0034] As the polypropylene-based resin, recycled resins may be used, or resins obtained by polymerizing raw materials derived from biomass such as plants may be used. These resins may be used alone, or may be mixed with resins polymerized from ordinary fossil fuels.

[0035] The base layer may be a stretched film or an unstretched film, but may be a stretched film from the viewpoint of oxygen barrier properties. Examples of the stretched film include a uniaxially stretched film and a biaxially stretched film, and a biaxially stretched film may improve heat resistance.

[0036] The substrate layer is, for example, a polyolefin film. In this embodiment, the substrate layer may include a polypropylene film or may be made of a polypropylene film. The polypropylene film constituting the substrate layer may be a stretched film or a non-stretched film. However, from the viewpoint of impact resistance, heat resistance, water resistance, dimensional stability, etc., the polypropylene film may be a stretched polypropylene film. This can suppress the substrate layer from being thermally fused in the heat sealing process during bag making. In addition, the gas barrier film can be more suitably used for applications in which a heat treatment such as a retort treatment or a boiling treatment is performed. The stretching method is not particularly limited, and any method such as stretching by inflation, uniaxial stretching, or biaxial stretching may be used as long as a film with stable dimensions can be supplied.

[0037] The base layer may contain known additives, for example, organic additives such as antioxidants, stabilizers, lubricants such as calcium stearate, fatty acid amides, and erucic acid amide, and antistatic agents, and inorganic additives such as particulate lubricants such as silica, zeolite, syloid, hydrotalcite, and silicon particles.

[0038] The thickness (total thickness) of the base layer is not particularly limited, and may be, for example, 3 to 200 μm, or 6 to 50 μm.

[0039] From the viewpoint of heat resistance of the gas barrier film, the polypropylene-based resin contained in the core layer may be crystalline polypropylene. From the viewpoint of further improving heat resistance, the polypropylene-based resin contained in the core layer may be homopolypropylene, which is a homopolymer of propylene. The polypropylene-based resin contained in the core layer may contain a mixture of homopolypropylene and a propylene-α-olefin random copolymer. The polypropylene-based resin contained in the core layer may contain 80% by mass or more of homopolypropylene, and may contain 100% by mass of homopolypropylene.

[0040] The first skin layer can reduce the difference between the shrinkage stress of the core layer and the shrinkage stress of the gas barrier coating layer due to the heat sterilization treatment, and prevent the occurrence of cracks in the gas barrier coating layer. Another layer having an adhesive function, including an acid-modified polyolefin, an ethylene-vinyl alcohol copolymer, a polyamide, etc., may be provided between the core layer and the first skin layer, but the core layer and the first skin layer may be in contact with each other without any other layer therebetween.

[0041] In order to improve the adhesion between the substrate layer and the vapor deposition layer, the first skin layer (the surface of the substrate layer facing the vapor deposition layer) may be subjected to a surface treatment such as plasma treatment or corona treatment.

[0042] The second skin layer can increase the lamination strength with the adjacent layer (outer layer film or sealant layer). Another layer may be provided between the core layer and the second skin layer as described above. Alternatively, the core layer and the second skin layer may be in contact with each other without another layer therebetween.

[0043] In order to increase the lamination strength between adjacent layers without providing a second skin layer, the surface of the core layer may be subjected to surface treatment such as plasma treatment or corona treatment, or an easy-adhesion coating layer may be provided.

[0044] The polypropylene-based resin contained in each skin layer may contain a propylene copolymer (a copolymer of propylene and another monomer) from the viewpoint of improving adhesion with the core layer. Examples of the other monomer include α-olefins such as ethylene, 1-butene, and 1-hexene. Specifically, the propylene copolymer may be a propylene-ethylene random copolymer, a propylene-ethylene block copolymer, a propylene-α-olefin copolymer, or the like. From the viewpoint of improving heat resistance, each skin layer may contain a propylene-α-olefin copolymer.

[0045] The content of the propylene monomer in the propylene copolymer may be 90 mol % or more, or may be 92 mol % or more, based on all monomers constituting the copolymer, from the viewpoint of improving heat resistance. The content of the propylene monomer in the propylene copolymer may be 99.8 mol % or less, or may be 99.5 mol % or less, based on all monomers constituting the copolymer, from the viewpoint of imparting flexibility.

[0046] The hardness and composite modulus of the core layer and each skin layer are measured by nanoindentation. Nanoindentation is a measurement method that performs a quasi-static indentation test on a measurement object to obtain the mechanical properties of the sample. The measurement device used is Hysitron TI-Premier (product name) manufactured by Bruker Japan Co., Ltd., and the indenter used is a Berkovich-type diamond indenter manufactured by Bruker Japan Co., Ltd.

[0047] The nanoindentation measurement is performed in displacement control mode by indenting to a depth of 30 nm at a indentation speed of 30 nm / sec, holding the maximum depth for 1 second, and then unloading at a speed of 30 nm / sec.

[0048] The measurement is performed by acquiring a shape image of the cross section of the sample using the shape measurement function of a measuring device that scans the sample surface with an indenter, and then specifying 20 points on the target layer at intervals of 1 μm or more from the shape image.

[0049] When calculating the hardness and composite elastic modulus, a standard sample of fused quartz is tested in advance to calibrate the relationship between the contact depth and the contact projected area of ​​the indenter and sample.Then, the unloading curve in the 60-95% range of the maximum load at the time of unloading is analyzed by the Oliver-Pharr method to calculate the hardness and composite elastic modulus.

[0050] The nanoindentation method is performed on the cross section of the substrate layer, which is embedded in resin and then cut to expose the cross section. When embedding in resin, corona treatment may be performed as a surface treatment on the front and back surfaces of the substrate layer to prevent peeling between the embedding resin and the substrate layer. The sample used for the measurement does not have to be in the form of only the substrate layer, and may be in the form of a gas barrier film or a packaging film.

[0051] The hardness of the core layer is 0.07 GPa or more. A core layer having a hardness in this range is resistant to heat and can suppress the shrinkage of the base material layer during heat sterilization treatment. The hardness of the core layer may be 0.072 GPa or more, or may be 0.075 GPa or more. The upper limit of the hardness is not particularly limited, but since a polypropylene-based resin is used as the material, it can be 0.2 GPa or less.

[0052] The hardness of the first skin layer is in the range of 0.02 to 0.15 GPa. When the hardness of the first skin layer is 0.02 GPa or more, the first skin layer is prevented from becoming too soft, and the adhesion and gas barrier properties are unlikely to deteriorate. When the hardness of the first skin layer is 0.15 GPa or less, the first skin layer is prevented from becoming too hard. This reduces the stress difference between the core layer and the gas barrier coating layer during the heat sterilization treatment, and the gas barrier properties are unlikely to deteriorate. In addition, the adhesion strength between the core layer and the first skin layer is unlikely to deteriorate. The hardness of the first skin layer may be 0.025 to 0.10 GPa, or 0.030 to 0.098 GPa.

[0053] The hardness of the second skin layer can be set to the same value as that of the first skin layer 11. This not only increases the lamination strength with the adjacent layers but also increases the adhesive strength with the core layer.

[0054] In order to reduce the shrinkage of the base material layer during heat sterilization and to maintain the adhesive strength between the layers, the hardness of the core layer is set to be the greatest in the base material layer. That is, the hardness of the core layer is set to be greater than the hardness of the first skin layer, and greater than the hardness of the second skin layer. The hardness of the first skin layer and the second skin layer may be the same or different.

[0055] The composite modulus of the core layer may be 2.0 GPa or more. A core layer having a composite modulus in this range is stronger against heat, so that it is easier to suppress the shrinkage of the base layer during heat sterilization treatment. The composite modulus of the core layer may be 2.1 GPa or more, or may be 2.13 GPa or more. The upper limit of the composite modulus is not particularly limited, but is 4.5 GPa or less because a polypropylene-based resin is used as the material.

[0056] The composite elastic modulus of the first skin layer may be in the range of 1.2 to 2.5 GPa. When the composite elastic modulus of the first skin layer is 1.2 GPa or more, the first skin layer is prevented from becoming too soft, and the adhesion and gas barrier properties are less likely to deteriorate. When the composite elastic modulus of the first skin layer is 2.5 GPa or less, the first skin layer is prevented from becoming too hard. This makes it easier to alleviate the stress difference between the core layer and the gas barrier coating layer during the heat sterilization treatment, and the gas barrier properties are less likely to deteriorate. In addition, the adhesion strength between the core layer and the first skin layer is less likely to deteriorate. The composite elastic modulus of the first skin layer may be 1.22 to 2.48 GPa, or 1.25 to 2.45 GPa.

[0057] The composite elastic modulus of the second skin layer can be set to the same value as that of the first skin layer, which not only increases the lamination strength between the adjacent layers but also increases the adhesive strength between the second skin layer and the core layer.

[0058] In order to reduce the shrinkage of the base layer during heat sterilization and to easily maintain the adhesive strength between the layers, the composite elastic modulus of the core layer may be set to be the largest in the base layer. That is, the composite elastic modulus of the core layer may be set to be greater than the composite elastic modulus of the first skin layer, and the composite elastic modulus of the core layer may be set to be greater than the composite elastic modulus of the second skin layer. The composite elastic moduli of the first skin layer and the second skin layer may be the same or different.

[0059] The method for adjusting the hardness and composite modulus of the core layer and each skin layer is not particularly limited. The hardness and composite modulus of each layer containing a polypropylene resin can be adjusted, for example, by adjusting the type of resin constituting each layer, the mixing ratio of multiple resins when multiple resins are used, the monomer ratio when a copolymer is used, and the manufacturing method of each layer.

[0060] The thickness of each skin layer may be 0.1 μm or more. This allows the skin layer to be uniformly laminated on the core layer, and the variation in the thickness of the skin layer can be suppressed. This also allows the stress on the deposition layer during the heat sterilization treatment to be sufficiently alleviated, and it is believed that the deterioration of the gas barrier property can be suppressed. From this viewpoint, the thickness of each skin layer is, for example, 0.3 μm or more.

[0061] The upper limit of the thickness of each skin layer is not particularly limited, but from the viewpoint of more sufficiently ensuring the heat resistance of the entire base layer, it is, for example, 2.0 μm or less, and may be 1.8 μm or less.

[0062] The ratio of the thickness of the first skin layer to the thickness of the core layer (thickness of the first skin layer / thickness of the core layer) may be 1 / 100 to 1 / 5, or 1 / 70 to 1 / 10. When the thickness ratio is within the above range, the heat resistance of the entire base layer can be more sufficiently ensured, and the adhesion between the layers in the gas barrier film and the packaging film can be further improved.

[0063] The ratio of the thickness of the second skin layer to the thickness of the core layer (thickness of the second skin layer / thickness of the core layer) may be 1 / 100 to 1 / 5, or 1 / 70 to 1 / 10. When the thickness ratio is within the above range, the heat resistance of the entire base layer can be more sufficiently ensured, and the adhesion between the layers in the gas barrier film and the packaging film can be further improved.

[0064] [Vapour-deposited layer] The deposition layer contains an inorganic oxide and is a layer provided on the base layer from the viewpoint of improving the gas barrier property against, for example, water vapor or oxygen. The deposition layer may be transparent. Examples of the inorganic oxide include aluminum oxide, silicon oxide, tin oxide, magnesium oxide, and mixtures thereof. From the viewpoint of heat resistance during heat sterilization treatment, at least one of aluminum oxide and silicon oxide may be used as the inorganic oxide.

[0065] The thickness of the deposition layer may be 5 to 300 nm. If the thickness of the deposition layer is 5 nm or more, the layer thickness is easily made uniform, and the function as a gas barrier film is more easily ensured. If the thickness of the deposition layer is 300 nm or less, flexibility is easily imparted to the deposition layer, and cracks are less likely to occur in the deposition layer even if external factors such as bending or pulling are applied after the layer is formed. From this viewpoint, the thickness of the deposition layer is, for example, 6 nm or more, and may be 150 nm or less, or may be 100 nm or less. The thickness of the deposition layer may be 5 to 80 nm, or 20 to 40 nm.

[0066] The deposition layer 2 can be formed by a normal vacuum deposition method. It is also possible to use other thin film formation methods such as sputtering, ion plating, plasma chemical vapor deposition (CVD), etc. However, in terms of productivity, the vacuum deposition method is currently superior.

[0067] The heating means for the vacuum deposition method may be any of the following: electron beam heating, resistance heating, and induction heating. Considering the wide range of options for evaporation materials, the electron beam heating may be used as the heating means.

[0068] In order to improve the adhesion between the deposition layer and the base layer and the density of the deposition layer, the deposition layer can be formed using a plasma assisted method or an ion beam assisted method. In addition, in order to increase the transparency of the deposition layer, reactive deposition in which various gases such as oxygen are blown in during deposition may be used.

[0069] [Anchor coat layer] An anchor coat layer can be further provided between the substrate layer and the deposition layer, which can further improve the adhesion between the two layers and the gas barrier properties after heat sterilization.

[0070] Examples of coating agents for providing the anchor coat layer include acrylic resins, epoxy resins, acrylic urethane resins, polyester polyurethane resins, polyether polyurethane resins, etc. From the viewpoints of heat resistance and interlayer adhesion strength, acrylic urethane resins and polyester polyurethane resins may be used as the coating agent.

[0071] The thickness of the anchor coat layer may be 0.05 to 2 μm. If the thickness of the anchor coat layer is 0.05 μm or more, it is possible to further improve the adhesion between the base layer and the deposition layer. Also, if the thickness of the anchor coat layer is 2 μm or less, it is easy to impart flexibility to the anchor coat layer, and it is easy to maintain the gas barrier properties even if external factors such as bending or pulling are applied after the layer is formed. From this viewpoint, the thickness of the anchor coat layer may be, for example, 0.08 μm or more and 1 μm or less.

[0072] [Gas barrier coating layer] The gas barrier coating layer is provided for the purpose of protecting the deposition layer and complementing the gas barrier property. The gas barrier coating layer may be made of a cured product of a composition containing a water-soluble polymer having a hydroxyl group and at least one selected from the group consisting of a metal alkoxide, a silane coupling agent, and a hydrolyzate thereof.

[0073] Examples of water-soluble polymers having a hydroxyl group include polyvinyl alcohol, polyvinylpyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, sodium alginate, etc. In particular, when polyvinyl alcohol (PVA) is used as a coating agent, the gas barrier property tends to be more excellent.

[0074] Examples of the metal alkoxide include compounds represented by the following general formula: M(OR 1 ) m (R 2 ) n-m In the above formula, R 1 is a monovalent organic group having 1 to 8 carbon atoms, and is an alkyl group such as a methyl group or an ethyl group (OR 1 R may be a hydrolyzable group. 2 is a monovalent organic group having 1 to 8 carbon atoms, and may be an alkyl group such as a methyl group or an ethyl group. M is an n-valent metal atom such as Si, Ti, Al, or Zr. m is an integer from 1 to n. 1 and R 2 If there are multiple, R 1 Friends or R 2 They may be the same or different.

[0075] Specific examples of metal alkoxides include tetraethoxysilane [Si(OC2H5)4], triisopropoxyaluminum [Al(O-2'-C3H7)3], etc. Tetraethoxysilane (TEOS) and triisopropoxyaluminum tend to be relatively stable in aqueous solvents after hydrolysis.

[0076] The silane coupling agent includes compounds represented by the following general formula: Si(OR 21 ) p (R 22 ) 3-p R 23 …(2) In the above formula, R 21 represents an alkyl group such as a methyl group or an ethyl group, and R 22represents a monovalent organic group such as an alkyl group, an aralkyl group, an aryl group, an alkenyl group, an alkyl group substituted with an acryloxy group, or an alkyl group substituted with a methacryloxy group, and R 23 represents a monovalent organic functional group, and p represents an integer of 1 to 3. 21 or R 22 If there are multiple, R 21 R 22 R may be the same or different. 23 Examples of the monovalent organic functional group represented by the formula (I) include a monovalent organic functional group containing a glycidyloxy group, an epoxy group, a mercapto group, a hydroxyl group, an amino group, an alkyl group substituted with a halogen atom, or an isocyanate group. Compounds obtained by converting these silane coupling agents into polymers such as dimers and trimers may also be used.

[0077] Specific examples of the silane coupling agent include vinyltrimethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropylmethyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, and 1,3,5-tris(3-methoxysilylpropyl)isocyanurate.

[0078] The gas barrier coating layer can be formed by coating the composition for forming the gas barrier coating layer on the deposition layer and then drying by heating. The composition for forming the gas barrier coating layer can be prepared by mixing at least one of a metal alkoxide and a silane coupling agent, or a pre-hydrolyzed version of these, with a water-soluble polymer dissolved in an aqueous solvent (water, a water / alcohol mixed solvent, etc.). This composition (mixed solution) can also contain known additives such as an isocyanate compound, a dispersant, a stabilizer, a viscosity modifier, and a colorant, as necessary, within the range that does not impair the gas barrier properties.

[0079] When PVA is used as the water-soluble polymer, the amount of PVA in the composition may be 20 to 70% by mass, or 25 to 60% by mass, based on the total solid content of the composition. When the amount of PVA is 20% by mass or more, the flexibility of the layer is maintained, and it becomes easier to form a gas barrier coating layer. On the other hand, when the amount of PVA is 70% by mass or less, it becomes easier to impart sufficient gas barrier properties to the gas barrier film.

[0080] When TEOS is used as the metal alkoxide, the amount of TEOS in the composition may be 30 to 80 mass % or 40 to 75 mass % based on the total solid content of the composition. When the amount of TEOS is 30 mass % or more, high gas barrier properties are easily achieved. On the other hand, when the amount of TEOS is 80 mass % or less, the flexibility of the layer is easily maintained. The amount of TEOS is calculated in terms of SiO2.

[0081] When isocyanurate silane is used as the silane coupling agent, the mass ratio may be 1 to 20 mass% or 5 to 15 mass% based on the total solid content of the composition. If the amount of isocyanurate silane is 1 mass% or more, hot water resistance is easily obtained and adhesion strength is not easily reduced. On the other hand, if the amount of isocyanurate silane is 20 mass% or less, the amount of other components in the composition is not too low, and as a result, high gas barrier properties are easily obtained.

[0082] The thickness of the gas barrier coating layer may be 0.1 to 5 μm. If the thickness of the gas barrier coating layer is 0.1 μm or more, high gas barrier properties are easily exhibited. If the thickness of the gas barrier coating layer is 5 μm or less, deterioration of the gas barrier properties due to cracking of the layer during coating can be suppressed. From this viewpoint, the thickness of the gas barrier coating layer may be, for example, 0.2 μm or more and 1 μm or less.

[0083] <Packaging film> Fig. 3 is a schematic cross-sectional view showing the packaging film according to the first embodiment. The packaging film 20 shown in Fig. 3 has a structure in which a sealant layer 23 is laminated on a gas barrier coating layer 3 of a gas barrier film 10a via an adhesive layer 24.

[0084] Fig. 4 is a schematic cross-sectional view showing a packaging film according to a modified example of the first embodiment. In the packaging film 30 shown in Fig. 4, the sealant layer 23 is laminated on the second skin layer 13 of the gas barrier film 10b via an adhesive layer 24, and the outer layer film (outermost layer) 22 is laminated on the gas barrier coating layer 3 of the gas barrier film 10b via a second adhesive layer 25. In the packaging film 30 shown in Fig. 4, the orientation of the gas barrier film 10b may be reversed. That is, the outer layer film (second base layer) 22 may be laminated on the second skin layer 13 of the gas barrier film 10b via the second adhesive layer 25, and the sealant layer 23 may be laminated on the gas barrier coating layer 3 of the gas barrier film 10b via the adhesive layer 24.

[0085] (Outer film) The outer layer film is a layer provided for the purpose of increasing the rigidity of the packaging bag. Therefore, the outer layer film can be called a second base layer. In order to make the packaging film a mono-material packaging material, the outer layer film contains a polyolefin resin. Examples of polyolefin resins include polyethylene and polypropylene, and polypropylene may be used from the viewpoint of retort treatment resistance. Here, the polypropylene may be either homopolypropylene or propylene copolymer, and homopolypropylene may be used from the viewpoint of heat resistance.

[0086] The outer layer film may be a stretched film or an unstretched film, but from the viewpoint of oxygen barrier properties, a stretched film is also preferred.

[0087] The thickness of the outer layer film is not particularly limited, but may be, for example, 15 to 200 μm.

[0088] (Sealant layer) The sealant layer contains a polyolefin resin. Specifically, examples of the polyolefin resin include ethylene resins such as low-density polyethylene resin (LDPE), medium-density polyethylene resin (MDPE), linear low-density polyethylene resin (LLDPE), ethylene-vinyl acetate copolymer (EVA), ethylene-α-olefin copolymer, and ethylene-(meth)acrylic acid copolymer, and polypropylene resins such as homopolypropylene resin (PP), propylene-ethylene random copolymer, propylene-ethylene block copolymer, and propylene-α-olefin copolymer, and mixtures thereof. The material of the sealant layer can be appropriately selected from the above-mentioned thermoplastic resins depending on the intended use and temperature conditions such as boiling and retorting.

[0089] The sealant layer may be a polyolefin film like the base layer. The sealant layer may be, for example, a resin layer having a single layer structure and mainly made of polypropylene, but is not limited thereto. The sealant layer may include a polypropylene film or may be made of a polypropylene film.

[0090] The thermoplastic resin constituting the sealant layer may be stretched or not. From the viewpoint of lowering the melting point and facilitating heat sealing, it may not be stretched. The polypropylene film constituting the sealant layer may be a non-stretched polypropylene film from the viewpoint of improving the sealability by heat sealing.

[0091] The thickness of the sealant layer is not particularly limited, but may be, for example, 15 to 200 μm.

[0092] (adhesive layer) The adhesive layer is for bonding the films together. Examples of adhesives constituting the adhesive layer include polyurethane resins in which a bifunctional or higher isocyanate compound is reacted with a base material such as polyester polyol, polyether polyol, acrylic polyol, or carbonate polyol. The various polyols may be used alone or in combination of two or more. From the viewpoint of heat resistance (resistance to retort treatment) during heat sterilization treatment, a two-liquid curing urethane adhesive may be used.

[0093] For the purpose of promoting adhesion, the polyurethane resin may be blended with a carbodiimide compound, an oxazoline compound, an epoxy compound, a phosphorus compound, a silane coupling agent, or the like. From the viewpoint of environmental consideration, the adhesive may be one whose polymer component is derived from biomass or has biodegradability. The adhesive may also be one having barrier properties.

[0094] The amount of adhesive applied is, for example, 0.5 to 10 g / m from the viewpoint of obtaining the desired adhesive strength, followability, processability, and the like. 2 It may be.

[0095] The thickness of the adhesive layer is, for example, 0.5 μm or more and 10 μm or less. When the thickness of the adhesive layer is 0.5 μm or more, peeling between the gas barrier coating layer and the sealant layer can be effectively suppressed. When the thickness of the adhesive layer is 10 μm or less, the packaging film can be easily made into a mono-material (details will be described later). The thickness of the adhesive layer may be 1 μm or more, 2 μm or more, 8 μm or less, 6 μm or less, or 5 μm or less.

[0096] (Second adhesive layer) The second adhesive layer is a layered member that bonds the gas barrier film and the outer film. The material of the adhesive contained in the second adhesive layer is the same as the material of the adhesive contained in the adhesive layer. Therefore, a description of the material contained in the second adhesive layer is omitted. The thickness of the second adhesive layer is the same as the thickness of the adhesive layer, for example, 0.5 μm or more and 10 μm or less.

[0097] (Polyolefin content) The total mass ratio of polyolefin (polypropylene in this embodiment) in the packaging film is 90 mass% or more. This allows the packaging film to be said to be a packaging material made of a single material (mono-material), and has excellent recyclability. From the viewpoint of further improving recyclability, the content of polyolefin in the packaging film may be 92.5 mass% or more, or may be 95 mass% or more, based on the total amount of the packaging film.

[0098] (Thermal shrinkage rate of base layer) After the base layer is exposed to 120°C for 15 minutes (hereinafter simply referred to as "after heating"), the heat shrinkage rate in the MD direction of the base layer calculated by the following formula (1) is 1% or more. For example, after the base layer or a gas barrier film including the base layer is heated in an oven at 120°C for 15 minutes, the heat shrinkage rate in the MD direction of the base layer calculated by the following formula (1) is 1% or more. From the viewpoints of reducing deformation during bag making and suppressing peeling between the gas barrier film and the sealant layer, the heat shrinkage rate in the MD direction is, for example, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, or 7% or less. For example, the heat shrinkage rate of a biaxially oriented polypropylene film is 1% or more, while the heat shrinkage rate of a PET film is less than 1%. Thermal shrinkage rate in MD direction (%) = (MD length before heating - MD length after heating) / MD length before heating × 100 ... (1)

[0099] After the heating, the heat shrinkage rate in the TD direction of the base layer calculated by the following formula (2) is not particularly limited, but is, for example, 1% or more. From the viewpoints of reducing deformation during bag making and suppressing peeling between the gas barrier film and the sealant layer, the heat shrinkage rate in the TD direction is, for example, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, or 7% or less. Thermal shrinkage rate in TD direction (%) = (length in TD direction before heating - length in TD direction after heating) / length in TD direction before heating × 100 ... (2)

[0100] (Hardness of adhesive layer) Considering the above-mentioned thermal shrinkage rate of the base material layer, in this embodiment, after the packaging film is subjected to retort treatment, the hardness of the adhesive layer is 0.1 MPa or more and less than 0.9 MPa. In this case, the adhesive layer can well follow the expansion and contraction of the base material layer accompanying heating treatment such as retort treatment and boiling treatment. Therefore, even if the above-mentioned heating treatment is performed on a packaging film including a base material layer having the above-mentioned thermal shrinkage rate, peeling between the gas barrier film and the sealant layer is unlikely to occur. In addition, cracking of the adhesive layer during cooling after the above-mentioned heating treatment, and damage to the gas barrier film (at least one of the deposition layer and the gas barrier coating layer) accompanying the cracking are suppressed. The hardness of the adhesive layer before the retort treatment is not particularly limited, but is, for example, 1.0 MPa or more.

[0101] The hardness of the adhesive layer can be controlled by the adhesive material, the amount of curing agent, the aging time, etc. The narrower the distance between the molecular chains of the adhesive, the harder the adhesive layer tends to be. The bulkier the adhesive, the softer the adhesive layer tends to be. The hardness of an aliphatic adhesive layer tends to be harder than that of an alicyclic or aromatic adhesive layer. The hardness of an alicyclic adhesive layer tends to be harder than that of an aromatic adhesive layer. The greater the amount of curing agent contained in the adhesive layer, the harder the adhesive layer tends to be. The longer the aging time, the harder the adhesive layer tends to be.

[0102] The hardness of the adhesive layer in the packaging film is obtained by measuring the hardness of the portion (exposed portion) exposed from the sealant layer. The removal of the sealant layer to expose the adhesive layer is performed, for example, using an oblique cutting device. In this embodiment, the hardness of the adhesive layer is obtained by measuring it by a nanoindentation method. The hardness of a sample such as an adhesive layer is calculated, for example, by the following method. First, fused quartz as a standard sample is tested in advance, and the relationship between the contact depth and the contact projected area of ​​the indenter and the sample is calibrated. Then, the unloading curve in the 20 to 95% region with respect to the maximum load at the time of unloading is analyzed by the Oliver-Pharr method to calculate the hardness of the sample.

[0103] (Outer film hardness) After the outer layer film is exposed to 120° C. for 15 minutes, the heat shrinkage rate in the MD direction of the outer layer film calculated by the above formula (1) is 1% or more. For example, after the outer layer film or a laminate of the outer layer film and the gas barrier film 10b is heated in an oven at 120° C. for 15 minutes, the heat shrinkage rate in the MD direction of the outer layer film calculated by the following formula (1) is 1% or more. The following heat shrinkage rate in the MD direction is, for example, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, or 7% or less.

[0104] After the above heating, the heat shrinkage rate in the TD direction of the outer layer film calculated by the above formula (2) is not particularly limited, but is, for example, 1% or more and 12% or less.

[0105] (Hardness of the second adhesive layer) In this modification, after the packaging film is subjected to retort treatment, the hardness of the second adhesive layer is 0.1 MPa or more and less than 0.9 MPa. In this case, the second adhesive layer can well follow the expansion and contraction of the outer layer film accompanying heat treatment such as retort treatment and boiling treatment. Therefore, even if the above heat treatment is performed on a packaging film including a second adhesive layer having the above-mentioned thermal shrinkage rate, peeling between the gas barrier film and the outer layer film is unlikely to occur. In addition, cracks in the second adhesive layer during cooling after the above heat treatment, and damage to the gas barrier film (at least one of the deposition layer and the gas barrier coating layer) accompanying the cracks are suppressed. The hardness of the second adhesive layer before the retort treatment is not particularly limited, but is, for example, 1.0 MPa or more.

[0106] The hardness of the second adhesive layer can be controlled by the adhesive material, the amount of curing agent, the aging time, etc. The narrower the distance between the molecular chains of the adhesive, the harder the second adhesive layer tends to be. The bulkier the adhesive, the softer the second adhesive layer tends to be. The hardness of an aliphatic second adhesive layer tends to be harder than that of an alicyclic or aromatic second adhesive layer. The hardness of an alicyclic second adhesive layer tends to be harder than that of an aromatic second adhesive layer. The greater the amount of curing agent contained in the second adhesive layer, the harder the second adhesive layer tends to be. The longer the aging time, the harder the second adhesive layer tends to be.

[0107] <Packaging bag> The packaging bag is made by forming the above-mentioned packaging film into a bag, and can contain contents such as food, medicine, etc.

[0108] The packaging bag may be one in which one packaging film is folded in half so that the sealant layers face each other, and then three sides are heat-sealed to form a bag shape, or two packaging materials are stacked so that the sealant layers face each other, and then four sides are heat-sealed to form a bag shape. The packaging bag may also have a shape having a bent portion (folded portion) such as a standing pouch. The packaging bag according to this embodiment can maintain high gas barrier properties even in a shape having a bent portion.

[0109] [Second embodiment] <Laminate> Fig. 5(a) is a schematic plan view of a laminate according to an embodiment, and Fig. 5(b) is a schematic cross-sectional view of the laminate according to an embodiment. The laminate 35 shown in Figs. 5(a) and (b) is a sheet-like member (gas barrier laminate) having gas barrier properties, and is a sheet-like packaging material used for manufacturing packaging bags, for example. The laminate 35 can be suitably used for applications in which heat treatment such as retort treatment and boiling treatment is performed. The laminate 35 may correspond to the packaging film of the first embodiment.

[0110] Retort processing is a method of sterilizing microorganisms such as mold, yeast, and bacteria under pressure to preserve foods, medicines, etc. Usually, a packaging bag containing food, etc. is sterilized under pressure at 105-140°C, 0.15-0.30 MPa, and 10-120 minutes. There are two types of retort devices: a steam type that uses heated steam and a hot water type that uses pressurized heated water, and they are used appropriately depending on the sterilization conditions of the food, etc. that will be the contents. Boiling processing is a method of sterilizing with moist heat to preserve foods, medicines, etc. Usually, depending on the contents, a packaging bag containing food, etc. is sterilized with moist heat at 60-100°C, atmospheric pressure, and 10-120 minutes. Boiling processing is usually performed using a hot water bath at 100°C or less. There are two types of methods: a batch type in which the bag is immersed in a hot water bath at a constant temperature and treated for a certain period of time, and then removed, and a continuous type in which the bag is passed through a hot water bath in a tunnel-like manner.

[0111] The laminate 35 includes a barrier layer 40, a sealant layer 50, and an adhesive layer 60. The barrier layer 40 and the sealant layer 50 are laminated together and bonded together by the adhesive layer 60. In the laminate 35, the barrier layer 40, the adhesive layer 60, and the sealant layer 50 are laminated in this order. Hereinafter, as shown in FIG. 5(a), the direction MD is defined as the flow direction (longitudinal direction) of the laminate 35, and the direction TD is defined as the width direction (short direction) of the laminate 35. In addition, the direction perpendicular to both the directions MD and TD is defined as the stacking direction of the members included in the laminate 35.

[0112] [Barrier layer 40] The barrier layer 40 is a member that functions as a support in the laminate 35, and exhibits gas barrier properties against gases such as water vapor and oxygen. The barrier layer 40 may correspond to the gas barrier film of the first embodiment. As shown in FIG. 5, the barrier layer 40 has a substrate 41, an adhesion layer 42, a deposition layer 43, and a barrier coat 44. In the barrier layer 40, the substrate 41, the adhesion layer 42, the deposition layer 43, and the barrier coat 44 are laminated in this order. Therefore, the adhesion layer 42 and the deposition layer 43 are located between the substrate 41 and the barrier coat 44 in the stacking direction, and the adhesion layer 42 is located between the substrate 41 and the deposition layer 43. In this embodiment, the barrier coat 44 of the barrier layer 40 is closest to the adhesive layer 60 in the stacking direction. Therefore, the substrate 41 of the barrier layer 40 is farthest from the adhesive layer 60 in the stacking direction.

[0113] [Base material 41] The substrate 41 is a plastic member (substrate layer) that functions as the outermost layer in the laminate 35. The thickness of the substrate 41 is not particularly limited. Depending on the application, the thickness can be 6 to 200 μm, but from the viewpoint of reducing materials to reduce the environmental load and from the viewpoint of obtaining excellent heat resistance, impact resistance, and excellent gas barrier properties, the thickness may be 9 to 50 μm, 12 to 38 μm, or 18 to 30 μm.

[0114] From the viewpoint of recycling suitability of the laminate 35, the base material 41 is, for example, a polyolefin film. In this embodiment, the base material 41 may include a polypropylene film or may be made of a polypropylene film. The polypropylene film may be an acid-modified polypropylene film obtained by graft-modifying polypropylene with an unsaturated carboxylic acid, an acid anhydride of an unsaturated carboxylic acid, an ester of an unsaturated carboxylic acid, or the like. In addition, as the polypropylene, a polypropylene-based resin such as a homopolypropylene resin (PP), a propylene-ethylene random copolymer, a propylene-ethylene block copolymer, or a propylene-α-olefin copolymer may be used.

[0115] The polypropylene film constituting the substrate 41 may contain various additives such as a flame retardant, a slip agent, an antiblocking agent, an antioxidant, a light stabilizer, a tackifier, and an antistatic agent.

[0116] The polypropylene film constituting the substrate 41 may be a stretched film or a non-stretched film. However, from the viewpoints of impact resistance, heat resistance, water resistance, dimensional stability, and the like, the polypropylene film may be a stretched polypropylene film. This can prevent the substrate 41 from being thermally fused in the heat sealing process during bag making. In addition, the laminate 35 can be more suitably used for applications in which a heat treatment such as a retort treatment or a boiling treatment is performed. The stretching method is not particularly limited, and any method may be used as long as a dimensionally stable film can be provided, such as stretching by inflation, uniaxial stretching, or biaxial stretching.

[0117] The lamination surface of the substrate 41 may be subjected to various pretreatments such as corona treatment, plasma treatment, and frame treatment within the scope that does not impair the barrier performance, or a coating layer such as an easy-adhesion layer may be provided.

[0118] [Adhesion layer] The adhesion layer 42 functions as a layer (anchor coat layer) capable of improving the adhesion performance of the deposition layer 43 on the substrate 41, and is provided directly on the substrate 41. Therefore, the adhesion layer 42 is located between the substrate 41 and the deposition layer 43. By providing the adhesion layer 42, the smoothness of the surface of the barrier layer 40 on which the deposition layer 43 is provided can be improved. Note that improved smoothness makes it easier to form the deposition layer 43 uniformly without defects, and makes it easier to exhibit high barrier properties. The adhesion layer 42 can be formed, for example, by using an anchor coat agent.

[0119] Examples of the anchor coating agent include polyester-based polyurethane resins, polyether-based polyurethane resins, etc. As the anchor coating agent, polyester-based polyurethane resins can be used from the viewpoints of heat resistance and interlayer adhesive strength.

[0120] The thickness of the adhesive layer 42 is not particularly limited, and may be in the range of 0.01 to 5 μm, 0.03 to 3 μm, or 0.05 to 2 μm. If the thickness of the adhesive layer 42 is equal to or greater than the lower limit, a more sufficient interlayer adhesive strength tends to be obtained, whereas if the thickness is equal to or less than the upper limit, the desired gas barrier properties tend to be easily achieved.

[0121] The method for applying the adhesive layer 42 onto the substrate 41 can be any known application method without any particular limitation, and examples of such methods include an immersion method (dipping method), a method using a spray, a coater, a printer, a brush, etc. In addition, examples of the types of coaters and printers used in these methods and the application methods thereof include gravure coaters such as direct gravure method, reverse gravure method, kiss reverse gravure method, and offset gravure method, reverse roll coaters, microgravure coaters, coaters combined with chamber doctor, air knife coaters, dip coaters, bar coaters, comma coaters, die coaters, etc.

[0122] The coating amount of the adhesive layer 42 is 1 m after the anchor coating agent is applied and dried. 2 Mass per unit is 0.01 to 5 g / m 2 Even 0.03 to 3 g / m 2 It is also acceptable. 1m after applying and drying the anchor coating agent 2 When the mass per unit area is equal to or greater than the lower limit, the film tends to be sufficiently formed, whereas when the mass per unit area is equal to or less than the upper limit, the film tends to be sufficiently dried and the solvent is less likely to remain.

[0123] The method for drying the adhesive layer 42 is not particularly limited, but examples thereof include a method of natural drying, a method of drying in an oven set at a predetermined temperature, and a method using a dryer attached to the coater, such as an arch dryer, a floating dryer, a drum dryer, an infrared dryer, etc. Furthermore, the drying conditions can be appropriately selected depending on the drying method, and for example, in a method of drying in an oven, drying may be performed at a temperature of 60 to 100° C. for about 1 second to 2 minutes.

[0124] A polyvinyl alcohol resin can be used instead of the polyurethane resin as the adhesive layer 42. The polyvinyl alcohol resin may be any resin having a vinyl alcohol unit obtained by saponifying a vinyl ester unit, and examples of the polyvinyl alcohol resin include polyvinyl alcohol (PVA) and ethylene-vinyl alcohol copolymer (EVOH).

[0125] Examples of PVA include resins obtained by homopolymerizing vinyl esters such as vinyl acetate, vinyl formate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl pivalate, and vinyl versatate, followed by saponification. PVA may be modified PVA that has been copolymerized or post-modified. Modified PVA can be obtained, for example, by copolymerizing a vinyl ester with an unsaturated monomer copolymerizable with the vinyl ester, followed by saponification. Examples of unsaturated monomers copolymerizable with vinyl ester include olefins such as ethylene, propylene, isobutylene, α-octene, α-dodecene, and α-octadecene; hydroxyl-containing α-olefins such as 3-buten-1-ol, 4-pentyn-1-ol, and 5-hexen-1-ol; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, maleic anhydride, itaconic acid, and undecylenic acid; nitriles such as acrylonitrile and methacrylonitrile; diacetone acrylamide, acrylonitrile, methacrylonitrile, and methacrylonitrile; and the like. amides such as arylamide and methacrylamide; olefin sulfonic acids such as ethylene sulfonic acid, allyl sulfonic acid, and methallyl sulfonic acid; vinyl compounds such as alkyl vinyl ethers, dimethylallyl vinyl ketone, N-vinylpyrrolidone, vinyl chloride, vinyl ethylene carbonate, 2,2-dialkyl-4-vinyl-1,3-dioxane, glycerin monoallyl ether, and 3,4-diacetoxy-1-butene; vinylidene chloride, 1,4-diacetoxy-2-butene, and vinylene carbonate.

[0126] The polymerization degree of PVA is, for example, 300 to 3000. If the polymerization degree is less than 300, the barrier property is likely to decrease, and if it exceeds 3000, the viscosity is too high and the coating suitability is likely to decrease. The saponification degree of PVA may be 90 mol% or more, 95 mol% or more, or 99 mol% or more. The saponification degree of PVA may be 100 mol% or less, or 99.9 mol% or less. The polymerization degree and saponification degree of PVA can be measured in accordance with the method described in JIS K 6726 (1994).

[0127] EVOH is generally obtained by saponifying a copolymer of ethylene and an acid vinyl ester such as vinyl acetate, vinyl formate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl pivalate, or vinyl versatate.

[0128] The degree of polymerization of EVOH is, for example, 300 to 3000. If the degree of polymerization is less than 300, the barrier property is likely to decrease, and if it exceeds 3000, the viscosity is too high and the coating suitability is likely to decrease. The degree of saponification of the vinyl ester component of EVOH may be 90 mol% or more, 95 mol% or more, or 99 mol% or more. The degree of saponification of EVOH may be 100 mol% or less, or 99.9 mol% or less. The degree of saponification of EVOH is determined by performing nuclear magnetic resonance (1H-NMR) measurement and measuring the peak area of ​​hydrogen atoms contained in the vinyl ester structure and the peak area of ​​hydrogen atoms contained in the vinyl alcohol structure.

[0129] The ethylene unit content of EVOH is, for example, 10 mol% or more, may be 15 mol% or more, may be 20 mol% or more, or may be 25 mol% or more. The ethylene unit content of EVOH may be 65 mol% or less, may be 55 mol% or less, or may be 50 mol% or less. When the ethylene unit content is 10 mol% or more, the gas barrier property or dimensional stability can be maintained well under high humidity. On the other hand, when the ethylene unit content is 65 mol% or less, the gas barrier property can be improved. The ethylene unit content of EVOH can be determined by NMR method.

[0130] When a polyvinyl alcohol resin is used as the adhesive layer 42, the adhesive layer 42 can be formed by coating a polyvinyl alcohol resin solution, multi-layer extrusion, or the like.

[0131] [Vapour-deposited layer 43] The deposition layer 43 is a layer (gas barrier layer) that exhibits gas barrier properties against water vapor and oxygen, and contains at least one of a metal and an inorganic oxide. The deposition layer 43 is provided directly on the adhesive layer 42. The deposition layer 43 may have a single-layer structure or a laminated structure. Therefore, the deposition layer 43 contains at least one of a metal deposition layer and an inorganic oxide layer. When the deposition layer 43 includes a metal deposition layer, examples of the metal included in the metal deposition layer include aluminum and stainless steel. When the deposition layer 43 includes an inorganic oxide layer, examples of the inorganic oxide included in the inorganic oxide layer include aluminum oxide, silicon oxide, magnesium oxide, and tin oxide. From the viewpoint of transparency and barrier properties, the inorganic oxide may be selected from the group consisting of aluminum oxide, silicon oxide, and magnesium oxide. In addition, from the viewpoint of excellent tensile stretchability during processing, the inorganic oxide layer may be a layer using silicon oxide. By using an inorganic oxide layer, high barrier properties can be obtained with a very thin layer within a range that does not affect the recyclability of the laminate 35.

[0132] When the deposition layer 43 is an inorganic oxide layer using silicon oxide, the O / Si ratio of the inorganic oxide layer is preferably 1.7 or more. When the O / Si ratio is 1.7 or more, the content ratio of metal Si is suppressed, and good transparency is easily obtained. The O / Si ratio may be 2.0 or less. When the O / Si ratio is 2.0 or less, the crystallinity of SiO is high, and the inorganic oxide layer is prevented from becoming too hard, and good tensile resistance is obtained. This makes it possible to suppress the occurrence of cracks in the inorganic oxide layer when the barrier coat 44 is laminated. In addition, even after forming into a packaging bag, the substrate 41 may shrink due to heat during boiling or retort treatment, but when the O / Si ratio is 2.0 or less, the inorganic oxide layer easily follows the above shrinkage, and the deterioration of the barrier property can be suppressed. From the viewpoint of obtaining these effects more fully, the O / Si ratio of the inorganic oxide layer may be 1.75 to 1.9 or 1.8 to 1.85.

[0133] When the deposition layer 43 is an inorganic oxide layer using silicon oxide, the O / Si ratio of the inorganic oxide layer can be determined by X-ray photoelectron spectroscopy (XPS). For example, the measurement can be performed using an X-ray photoelectron spectrometer (manufactured by JEOL Ltd., product name: JPS-90MXV) as a measuring device, a non-monochromated MgKα (1253.6 eV) X-ray source, and an X-ray output of 100 W (10 kV-10 mA). For quantitative analysis to determine the O / Si ratio, relative sensitivity factors of 2.28 for O1s and 0.9 for Si2p can be used.

[0134] The thickness of the deposition layer 43 is, for example, 5 nm or more and 80 nm or less. When the thickness of the deposition layer 43 is 5 nm or more, sufficient water vapor barrier properties can be obtained. When the thickness of the deposition layer 43 is 80 nm or less, the occurrence of cracks due to deformation caused by internal stress of the thin film can be suppressed, and the deterioration of the water vapor barrier properties can be suppressed. Note that, when the thickness of the deposition layer 43 exceeds 80 nm, costs tend to increase due to an increase in the amount of material used and a prolonged film formation time, and this is not preferable from an economical point of view. From the same viewpoint as above, the thickness of the deposition layer 43 may be 20 nm or more and 40 nm or less.

[0135] The deposition layer 43 can be formed by, for example, vacuum deposition. In the vacuum deposition, physical vapor deposition or chemical vapor deposition can be used. Examples of physical vapor deposition include, but are not limited to, vacuum deposition, sputtering, and ion plating. Examples of chemical vapor deposition include, but are not limited to, thermal CVD, plasma CVD, and photo CVD.

[0136] In the vacuum film formation, a resistance heating vacuum deposition method, an EB (Electron Beam) heating vacuum deposition method, an induction heating vacuum deposition method, a sputtering method, a reactive sputtering method, a dual magnetron sputtering method, a plasma enhanced chemical vapor deposition method (PECVD method), etc. may be used. However, in terms of productivity, the vacuum deposition method is likely to be the most excellent at present. As a heating means for the vacuum deposition method, any of an electron beam heating method, a resistance heating method, and an induction heating method may be used.

[0137] [Barrier Coat 44] The barrier coat 44 is a coating layer having gas barrier properties (gas barrier coating layer) and is provided on the substrate 41. The barrier coat 44 is a layer formed using a composition for forming a gas barrier coating layer (hereinafter also referred to as a coating agent) containing at least one selected from the group consisting of a hydroxyl group-containing polymer compound, a metal alkoxide, a silane coupling agent, and hydrolysates thereof, for example.

[0138] From the viewpoint of more fully maintaining the gas barrier property after hot water treatment such as retort treatment, the coating agent may contain at least a silane coupling agent or a hydrolyzate thereof, or may contain at least one selected from the group consisting of a hydroxyl group-containing polymer compound, a metal alkoxide, and their hydrolyzates, and a silane coupling agent or a hydrolyzate thereof, or may contain a hydroxyl group-containing polymer compound or a hydrolyzate thereof, a metal alkoxide or a hydrolyzate thereof, and a silane coupling agent or a hydrolyzate thereof. The coating agent can be prepared, for example, by mixing a metal alkoxide and a silane coupling agent directly or after being previously treated by hydrolysis, into a solution in which a hydroxyl group-containing polymer compound, which is a water-soluble polymer, is dissolved in an aqueous (water or water / alcohol mixture) solvent.

[0139] A detailed description will be given of each component contained in the coating agent for forming the barrier coat 44. Examples of hydroxyl-containing polymer compounds used in the coating agent include polyvinyl alcohol, polyvinylpyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, sodium alginate, etc. Among these, when polyvinyl alcohol (PVA) is used in the coating agent for the barrier coat 44, the gas barrier properties tend to be particularly excellent.

[0140] In order to obtain excellent gas barrier properties, the barrier coat 44 may be formed from a composition containing at least one selected from the group consisting of metal alkoxides represented by the general formula (I) shown in the above embodiment and their hydrolysates.

[0141] Specific examples of metal alkoxides include tetraethoxysilane [Si(OC2H5)4], triisopropoxyaluminum [Al(O-2'-C3H7)3], etc. Tetraethoxysilane and triisopropoxyaluminum tend to be relatively stable in aqueous solvents after hydrolysis.

[0142] The silane coupling agent may be the compound represented by the above general formula (II) shown in the above embodiment.

[0143] Specific examples of the silane coupling agent include vinyltrimethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropyltrimethoxysilane, glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and γ-methacryloxypropylmethyldimethoxysilane.

[0144] The silane coupling agent may also be a polymer formed by polymerizing the compound represented by the general formula (II) above. The polymer may be a trimer or 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate. This is a condensation polymer of 3-isocyanate alkylalkoxysilane. It is known that the isocyanate moiety of this 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate is chemically non-reactive, but the reactivity is ensured by the polarity of the nurate moiety. In general, it is added to adhesives, etc., in the same manner as 3-isocyanate alkylalkoxysilane, and is known as an adhesion improver. Therefore, by adding 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate to a hydroxyl group-containing polymer compound, the water resistance of the gas barrier coating layer can be improved by hydrogen bonding. 3-isocyanate alkyl alkoxysilanes are highly reactive and have low liquid stability, whereas 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurates are not water-soluble due to the polarity of the nurate moiety, but are easily dispersed in aqueous solutions and can maintain a stable liquid viscosity. In addition, the water resistance of 3-isocyanate alkyl alkoxysilanes is equivalent to that of 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurates.

[0145] 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate may be produced by thermal condensation of 3-isocyanatepropylalkoxysilane, and may contain the raw material 3-isocyanatepropylalkoxysilane, but this is not a problem. 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate or 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate may be used. This methoxy group has a fast hydrolysis rate, and those containing propyl groups are relatively inexpensive, so 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate is advantageous in practical use.

[0146] Furthermore, known additives such as an isocyanate compound, a dispersant, a stabilizer, a viscosity adjuster, and a colorant can be added to the coating agent as needed, provided that the gas barrier properties are not impaired.

[0147] The thickness of the barrier coat 44 may be 50 to 1000 nm, or 100 to 500 nm. If the thickness of the barrier coat 44 is 50 nm or more, there is a tendency that more sufficient gas barrier properties can be obtained, and if it is 1000 nm or less, there is a tendency that sufficient flexibility can be maintained.

[0148] The coating liquid for forming the barrier coat 44 can be applied by, for example, dipping, roll coating, gravure coating, reverse gravure coating, air knife coating, comma coating, die coating, screen printing, spray coating, gravure offset, etc. The coating film obtained by applying this coating liquid can be dried by, for example, hot air drying, hot roll drying, high frequency irradiation, infrared irradiation, UV irradiation, or a combination thereof.

[0149] The temperature for drying the coating film can be, for example, 50 to 150° C., or may be 70 to 100° C. By keeping the drying temperature within the above range, the occurrence of cracks in the deposition layer 43 and the barrier coat 44 can be further suppressed, and excellent barrier properties can be exhibited.

[0150] The barrier coat 44 may be formed using a coating agent containing a polyvinyl alcohol resin and a silane compound. The coating agent may contain an acid catalyst, an alkali catalyst, a photopolymerization initiator, etc., as necessary.

[0151] The polyvinyl alcohol resin is as described above. Examples of the silane compound include a silane coupling agent, polysilazane, and siloxane, and more specifically, examples of the silane compound include tetramethoxysilane, tetraethoxysilane, glycidoxypropyltrimethoxysilane, acryloxypropyltrimethoxysilane, and hexamethyldisilazane.

[0152] [Print layer] The laminate 35 may include a printing layer. The printing layer can be provided, for example, on at least one surface of the substrate 41. The printing layer is provided at a position visible from the outside of the laminate 35 for the purpose of displaying information about the contents, identifying the contents, improving concealment, or improving the design of the packaging bag. The printing method and printing ink are not particularly limited, and are appropriately selected from known printing methods and printing inks in consideration of printability on the film, design such as color tone, adhesion, safety as a food container, and the like. Examples of printing methods that can be used include gravure printing, offset printing, gravure offset printing, flexographic printing, and inkjet printing. Among them, gravure printing is likely to be used from the viewpoints of productivity and high definition of the image.

[0153] In order to improve the adhesion of the printed layer, the surface of the layer on which the printed layer is to be formed may be subjected to various pretreatments such as corona treatment, plasma treatment, and frame treatment, or a coating layer such as an easy-adhesion layer may be provided.

[0154] [Sealant layer 50] The sealant layer 50 is a layer that imparts heat sealing properties to the laminate 35. From the viewpoint of recycling suitability of the laminate 35, the sealant layer 50 is a polyolefin film similar to the substrate 41. In this embodiment, the sealant layer 50 has a single-layer structure and is a resin layer mainly made of polypropylene, but is not limited thereto. The sealant layer 50 may include a polypropylene film or may be made of a polypropylene film.

[0155] The polypropylene film may be an acid-modified polypropylene film obtained by graft-modifying polypropylene with an unsaturated carboxylic acid, an acid anhydride of an unsaturated carboxylic acid, an ester of an unsaturated carboxylic acid, etc. As the polypropylene, a polypropylene-based resin such as a homopolypropylene resin (PP), a propylene-ethylene random copolymer, a propylene-ethylene block copolymer, or a propylene-α-olefin copolymer can be used.

[0156] The polypropylene film constituting the sealant layer 50 may be a non-oriented polypropylene film from the viewpoint of improving the sealing performance by heat sealing.

[0157] The polypropylene film constituting the sealant layer 50 may contain various additives such as a flame retardant, a slip agent, an antiblocking agent, an antioxidant, a light stabilizer, a tackifier, and an antistatic agent.

[0158] The thickness of the sealant layer 50 is determined depending on the weight of the contents, the shape of the packaging bag, etc., but may be generally 30 to 150 μm, or may be 50 to 80 μm.

[0159] The sealant layer 50 can be formed by any of the known lamination methods, such as a dry lamination method in which a film-like sealant layer made of the above-mentioned polypropylene is bonded with an adhesive such as a one-component curing or two-component curing urethane adhesive, a non-solvent dry lamination method in which a film-like sealant layer is bonded with a solvent-free adhesive, and an extrusion lamination method in which the above-mentioned polypropylene is heated and melted, extruded into a curtain shape, and bonded together.

[0160] Among the above-mentioned forming methods, the dry lamination method has high resistance to retort treatment, particularly high-temperature hot water treatment at 120° C. or higher. On the other hand, if the packaging bag is used for an application in which it is treated at a temperature of 85° C. or lower, the lamination method is not particularly limited.

[0161] [Adhesive layer 60] The adhesive layer 60 is a layered member that bonds the barrier layer 40 and the sealant layer 50. For example, polyester-isocyanate resin, urethane resin, polyether resin, etc. can be used as the adhesive material contained in the adhesive layer 60. To use the packaging bag for retort applications, a two-liquid curing urethane adhesive that is resistant to retort can be used. From the viewpoint of environmental consideration, the adhesive does not need to contain 3-glycidyloxypropyltrimethoxysilane (GPTMS). The adhesive layer 60 does not need to contain chlorine. In this case, it is possible to suppress the coloring of the adhesive forming the adhesive layer 60, the regenerated resin after recycling, and the generation of odor due to heat treatment. From the viewpoint of environmental consideration, the adhesive layer 60 may be formed of a biomass material and may not contain a solvent.

[0162] The thickness of the adhesive layer 60 is 0.5 μm or more and 10 μm or less. When the thickness of the adhesive layer 60 is 0.5 μm or more, peeling between the barrier layer 40 and the sealant layer 50 can be effectively suppressed. When the thickness of the adhesive layer 60 is 10 μm or less, the laminate 35 can be easily made into a mono-material (details will be described later). The thickness of the adhesive layer 60 may be 1 μm or more, 2 μm or more, 8 μm or less, 6 μm or less, or 5 μm or less.

[0163] [Polyolefin content] The total mass ratio of polyolefin (polypropylene in this embodiment) in the laminate 35 is 90 mass% or more. This allows the laminate 35 to be said to be a packaging material made of a single material (mono-material), and has excellent recyclability. From the viewpoint of further improving recyclability, the content of polyolefin in the laminate 35 may be 92.5 mass% or more, or may be 95 mass% or more, based on the total amount of the laminate 35.

[0164] [Thermal shrinkage rate of base material 41] After the substrate 41 is exposed to 120°C for 15 minutes (hereinafter simply referred to as "after heating"), the heat shrinkage rate in the MD direction of the substrate 41 calculated by the above formula (1) described in the first embodiment is 1% or more. For example, after the substrate 41 or the barrier layer 40 including the substrate 41 is heated in an oven at 120°C for 15 minutes, the heat shrinkage rate in the MD direction of the substrate 41 calculated by the following formula (1) is 1% or more. From the viewpoints of reducing deformation during bag making and suppressing peeling between the barrier layer 40 and the sealant layer 50, the heat shrinkage rate in the MD direction is, for example, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, or 7% or less. For example, the heat shrinkage rate of a biaxially oriented polypropylene film is 1%, while the heat shrinkage rate of a PET film is less than 1%.

[0165] After the heating, the heat shrinkage rate in the TD direction of the substrate 41 calculated by the formula (2) described in the first embodiment is not particularly limited, but is, for example, 1% or more. From the viewpoints of reducing deformation during bag making and suppressing peeling between the barrier layer 40 and the sealant layer 50, the heat shrinkage rate in the TD direction is, for example, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, or 7% or less.

[0166] [Hardness of adhesive layer 60] Considering the above-mentioned thermal shrinkage rate of the base material 41, in this embodiment, after the laminate 35 is subjected to the retort treatment, the hardness of the adhesive layer 60 is 0.1 MPa or more and less than 0.9 MPa. In this case, the adhesive layer 60 can well follow the expansion and contraction of the base material 41 accompanying the heating treatment such as the retort treatment and the boiling treatment. Therefore, even if the laminate 35 including the base material 41 having the above-mentioned thermal shrinkage rate is subjected to the above-mentioned heating treatment, peeling between the barrier layer 40 and the sealant layer 50 is unlikely to occur. In addition, the occurrence of cracks in the adhesive layer 60 during cooling after the above-mentioned heating treatment, and the occurrence of damage to the barrier layer 40 (at least one of the adhesion layer 42, the deposition layer 43, and the barrier coat 44) accompanying the occurrence of the cracks are suppressed. The hardness of the adhesive layer 60 before the retort treatment is not particularly limited, but is, for example, 1.0 MPa or more.

[0167] The hardness of the adhesive layer 60 can be controlled by the adhesive material, the amount of curing agent, the aging time, etc. The narrower the distance between the molecular chains of the adhesive, the harder the adhesive layer 60 tends to be. The bulkier the adhesive, the softer the adhesive layer 60 tends to be. The hardness of an aliphatic adhesive layer 60 tends to be harder than an alicyclic or aromatic adhesive layer 60. The hardness of an alicyclic adhesive layer 60 tends to be harder than an aromatic adhesive layer 60. The greater the amount of curing agent contained in the adhesive layer 60, the harder the adhesive layer 60 tends to be. The longer the aging time, the harder the adhesive layer 60 tends to be.

[0168] The hardness of the adhesive layer 60 in the laminate 35 is obtained by measuring the hardness of the portion (exposed portion) exposed from the sealant layer 50. Removal of the sealant layer 50 to expose the adhesive layer 60 is performed, for example, using an oblique cutting device. In this embodiment, the hardness of the adhesive layer 60 is obtained by measuring it using a nanoindentation method. The nanoindentation method is a measurement method for acquiring mechanical properties of a sample by performing a quasi-static indentation test using an indenter on a target measurement object (sample). The hardness of a sample such as the adhesive layer 60 is calculated, for example, by the following method. First, fused quartz, which is a standard sample, is tested in advance to calibrate the relationship between the contact depth and the contact projected area of ​​the indenter and the sample. Then, the unloading curve in the 20 to 95% region with respect to the maximum load at the time of unloading is analyzed by the Oliver-Pharr method to calculate the hardness of the sample.

[0169] <Packaging bag> An example of a packaging bag made from the laminate 35 will be described below with reference to Fig. 6. Fig. 6 is a schematic plan view of an example of a packaging bag. The packaging bag 100 shown in Fig. 6 is formed into a bag shape by, for example, sealing the ends of the laminate 35 that has been folded in half to sandwich the contents therebetween.

[0170] The packaging bag 100 is a three-sided bag having a main body 101 in which the contents are accommodated, a sealed portion 102 located at an end of the main body 101, and a folded portion 103 where the laminate 35 is folded. The shape of the main body 101 is not particularly limited, and may be rectangular when viewed from a predetermined direction. At least a part of the outer surface of the main body 101 may be printed. The main body 101 may accommodate a specific gas such as nitrogen in addition to the contents. The sealed portion 102 is a portion where a part of the sealant layer 50 included in the laminate 35 and another part are bonded together. In the sealed portion 102, a part of the sealant layer 50 included in the laminate 35 and another part are in close contact with each other. The sealed portion 102 is formed, for example, by heating and compressing (i.e., heat sealing) a part of the sealant layer 50 included in the laminate 35 and another part, but is not limited thereto. For example, the sealed portion 102 may be formed by cold sealing or the like. In the packaging bag 100, the folded portion 103 forms one side of the main body portion 101, and the sealed portion 102 forms the remaining three sides of the main body portion 101. Both ends of the folded portion 103 and the sealed portion 102 overlap with each other.

[0171] After performing retort treatment on the laminate 35 according to the present embodiment described above, the hardness of the adhesive layer 60 measured by a nanoindentation method is 0.1 MPa or more and less than 0.9 MPa. As a result, even if the substrate 41 expands or contracts due to retort treatment, the adhesive layer 60 can follow suit by using a substrate 41 having a thermal shrinkage rate of 1% or more in the MD direction. This makes it possible to suppress damage to the barrier coat 44 due to cracks in the adhesive layer 60. Therefore, it is possible to provide a laminate 35 that can exhibit good gas barrier properties (particularly oxygen permeation prevention performance) even after retort treatment.

[0172] In one example, the barrier layer 40 has an adhesion layer 42 and a deposition layer 43 located between the substrate 41 and the barrier coat 44, and the adhesion layer 42 is located between the substrate 41 and the deposition layer 43. Therefore, compared to a case where the barrier layer has only the substrate 41 and the barrier coat 44, the gas barrier property of the laminate 35 can be improved.

[0173] In one example, the thickness of the deposition layer 43 may be 5 nm or more and 80 nm or less. In this case, the gas barrier properties can be improved while preventing cracks in the deposition layer 43.

[0174] In one example, the thickness of the adhesive layer 60 may be 0.5 μm or more and 10 μm or less. In this case, the laminate 35 can be easily made into a mono-material while effectively suppressing peeling between the barrier layer 40 and the sealant layer 50.

[0175] In one example, each of the substrate 41 and the sealant layer 50 is a polyolefin film, and the total mass ratio of polyolefin in the laminate 35 may be 90 mass % or more. In this case, a mono-material structure is realized.

[0176] In one example, the substrate 41 may be a stretched polypropylene film, and the sealant layer 50 may be a non-stretched polypropylene film. In this case, the laminate 35 has excellent heat resistance against retort treatment and the like.

[0177] Next, a modified example of the second embodiment will be described with reference to Fig. 7. In the following, descriptions that overlap with the above embodiment will be omitted, and only differences from the above embodiment will be described. In other words, the descriptions of the above embodiment may be used appropriately in the modified example to the extent technically possible.

[0178] FIG. 7 is a schematic cross-sectional view showing a laminate according to a modified example. As shown in FIG. 7, the laminate (packaging film) 35A has, in addition to the barrier layer 40, the sealant layer 50, and the adhesive layer 60, an outermost layer 70 overlapping the barrier layer 40, and a second adhesive layer 60A bonding the outermost layer 70 and the barrier layer 40. In this modified example, the sealant layer 50, the adhesive layer 60, the barrier layer 40, the second adhesive layer 60A, and the outermost layer 70 are laminated in this order. In addition, the adhesive layer 60, the substrate 41, the adhesion layer 42, the deposition layer 43, the barrier coat 44, the second adhesive layer 60A, and the outermost layer 70 are laminated in this order. Therefore, the adhesive layer 60 bonds the substrate 41 and the sealant layer 50, and the second adhesive layer 60A bonds the barrier coat 44 and the outermost layer 70. In this modified example, the barrier layer 40 functions as an intermediate layer in the laminate 35A.

[0179] [Outermost layer 70] The outermost layer 70 is a plastic member that functions as the outermost member in the laminate 35A. The outermost layer 70 has the same function and performance as the base material 41. For example, the thickness of the outermost layer 70 is approximately the same as the thickness of the base material 41. From the viewpoint of the recyclability of the laminate 35A, the outermost layer 70 is, for example, a polyolefin film. From the viewpoint of heat resistance, the outermost layer 70 may include a polypropylene film or may be made of a polypropylene film.

[0180] In this modification, after the outermost layer 70 is exposed to 120° C. for 15 minutes, the heat shrinkage rate in the MD direction of the outermost layer 70 calculated by the above formula (1) is 1% or more. For example, after the outermost layer 70 or a laminate of the outermost layer 70 and the barrier layer 40 is heated in an oven at 120° C. for 15 minutes, the heat shrinkage rate in the MD direction of the outermost layer 70 calculated by the above formula (1) is 1% or more. The heat shrinkage rate in the MD direction is, for example, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, or 7% or less.

[0181] After the above heating, the thermal shrinkage rate in the TD direction of the outermost layer 70 calculated by the above formula (2) is not particularly limited, but is, for example, 1% or more and 12% or less.

[0182] [Second adhesive layer 60A] The second adhesive layer 60A is a layered member that bonds the barrier layer 40 and the outermost layer 70. The material of the adhesive contained in the second adhesive layer 60A is the same as the material of the adhesive contained in the adhesive layer 60. The thickness of the second adhesive layer 60A is the same as the thickness of the adhesive layer 60, and is 0.5 μm or more and 10 μm or less. In this modification, after the retort treatment is performed on the laminate 35A, the hardness of the second adhesive layer 60A is 0.1 MPa or more and less than 0.9 MPa. In this case, the second adhesive layer 60A can well follow the expansion and contraction of the outermost layer 70 accompanying the heating treatment such as the retort treatment and the boiling treatment. Therefore, even if the above heating treatment is performed on the laminate 35A including the second adhesive layer 60A having the above-mentioned thermal shrinkage rate, peeling between the barrier layer 40 and the outermost layer 70 is unlikely to occur. In addition, the occurrence of cracks in the second adhesive layer 60A during cooling after the heat treatment and the occurrence of damage to the barrier layer 40 (at least one of the adhesion layer 42, the deposition layer 43, and the barrier coat 44) due to the occurrence of cracks are suppressed. The hardness of the second adhesive layer 60A before the retort treatment is not particularly limited, but is, for example, 1.0 MPa or more.

[0183] The hardness of the second adhesive layer 60A can be controlled by the material of the adhesive, the amount of the curing agent, the aging time, and the like. The narrower the distance between the molecular chains of the adhesive, the harder the second adhesive layer 60A tends to be. The bulkier the adhesive, the softer the second adhesive layer 60A tends to be. The hardness of the aliphatic second adhesive layer 60A tends to be harder than that of the alicyclic or aromatic second adhesive layer 60A. The hardness of the alicyclic second adhesive layer 60A tends to be harder than that of the aromatic second adhesive layer 60A. The larger the amount of curing agent contained in the second adhesive layer 60A, the harder the second adhesive layer 60A tends to be. The longer the aging time, the harder the second adhesive layer 60A tends to be.

[0184] The above-described modified example also exerts the same effects as those of the second embodiment. In addition, the barrier layer 40 can be protected by the outermost layer .

[0185] The gas barrier film, packaging film, and packaging bag according to one aspect of the present disclosure are as described in, for example, [1] to

[19] below, and have been described in detail based on the above embodiment and the above modified examples. [1] A substrate layer containing a polypropylene-based resin, a vapor deposition layer containing an inorganic oxide, and a gas barrier coating layer, in this order; The substrate layer includes a first skin layer and a core layer, and the deposition layer is formed on the first skin layer side. A gas barrier film, wherein the hardness of the first skin layer is 0.02 to 0.15 GPa, and the hardness of the core layer is 0.07 GPa or more, as measured by a nanoindentation method, and the hardness of the core layer is greater than the hardness of the first skin layer. [2] The gas barrier film according to [1], wherein the first skin layer comprises a propylene-α-olefin copolymer. [3] The gas barrier film according to [1] or [2], wherein the ratio of the thickness of the first skin layer to the thickness of the core layer is 1 / 100 to 1 / 5. [4] The gas barrier film according to any one of [1] to [3], wherein the composite elastic modulus of the first skin layer is 1.2 to 2.5 GPa, and the composite elastic modulus of the core layer is 2.0 GPa or more, as measured by a nanoindentation method. [5] The gas barrier film according to any one of [1] to [4], wherein the inorganic oxide comprises at least one of aluminum oxide and silicon oxide. [6] The gas barrier film according to any one of [1] to [5], wherein the gas barrier coating layer comprises a cured product of a composition containing a water-soluble polymer having a hydroxyl group and at least one selected from the group consisting of a metal alkoxide, a silane coupling agent, and a hydrolysate thereof. [7] The gas barrier film according to any one of [1] to [6], further comprising an anchor coat layer between the base layer and the deposition layer. [8] The gas barrier film according to any one of [1] to [7], wherein the base layer comprises the first skin layer, the core layer, and a second skin layer in this order. [9] The gas barrier film according to [8], wherein the second skin layer comprises a propylene-α-olefin copolymer.

[10] The gas barrier film according to [8] or [9], wherein the hardness of the second skin layer is 0.02 to 0.15 GPa as measured by a nanoindentation method.

[11] The gas barrier film according to any one of [1] to

[10] , wherein the thickness of the vapor deposition layer is from 5 nm to 80 nm.

[12] A gas barrier film according to any one of [1] to

[11] , a sealant layer overlying the gas barrier coating layer; an adhesive layer that bonds the gas barrier coating layer and the sealant layer and contains a two-component curing urethane adhesive, A packaging film, wherein after the packaging film is subjected to a retort treatment, the hardness of the adhesive layer measured by a nanoindentation method is 0.1 MPa or more and less than 0.9 MPa.

[13] The packaging film described in

[12] , wherein the hardness of the adhesive layer measured by nanoindentation method before the retort treatment is 1.0 MPa or more.

[14] The packaging film described in

[12] or

[13] , wherein the thickness of the adhesive layer is 0.5 μm or more and 10 μm or less.

[15] Each of the base layer and the sealant layer is a polyolefin film; The packaging film according to any one of

[12] to

[14] , wherein the total mass ratio of the polyolefin in the packaging film is 90 mass % or more.

[16] The base layer is a stretched polypropylene film, The packaging film according to any one of

[12] to

[15] , wherein the sealant layer is a non-oriented polypropylene film.

[17] An outermost layer overlying the base layer; and a second adhesive layer that bonds the outermost layer and the base layer; Further equipped with the adhesive layer bonds the base layer and the sealant layer; The packaging film according to any one of

[12] to

[16] , wherein the second adhesive layer bonds the base material layer and the outermost layer.

[18] After exposing the outermost layer to 120°C for 15 minutes, the outermost layer has a thermal shrinkage rate in the MD direction calculated by the following formula (1) of 1% or more, The packaging film described in

[17] , wherein after the packaging film is subjected to a retort treatment, the hardness of the second adhesive layer measured by a nanoindentation method is 0.1 MPa or more and less than 0.9 MPa. Thermal shrinkage rate in MD direction (%) = (MD length before heating - MD length after heating) / MD length before heating × 100 ... (1)

[19] A packaging bag made from the packaging film according to any one of

[12] to

[18] .

[0186] However, one aspect of the present disclosure is not limited to the above embodiment, the above modified example, and the above [1] to

[19] . One aspect of the present disclosure can be further modified without departing from the gist of the present disclosure.

[0187] In the second embodiment and its modified examples, the total mass ratio of polypropylene in the laminate may be 90% by mass or more. Therefore, for example, in the laminate according to the modified example, the mass ratio of polypropylene in either the base material or the outermost layer may be less than 90% by mass. Alternatively, in the laminate, the mass ratio of polypropylene in the barrier layer may be less than 90% by mass.

[0188] In the second embodiment and its modified example, an anchor coat layer and a vapor deposition layer are provided on a substrate, but the present invention is not limited thereto. For example, a vapor deposition layer may be provided on a sealant layer. In this case, an anchor coat layer may be provided between the sealant layer and the vapor deposition layer. In this case, the sealant layer and the anchor coat layer may be coextrusion layers. Alternatively, an anchor coat layer and a vapor deposition layer may be included on the substrate, and a vapor deposition layer may be provided on the sealant layer. Alternatively, an anchor coat layer may not be provided. EXAMPLES

[0189] The present disclosure will be described in more detail below with reference to examples, but the present disclosure is not limited to these examples. First, Examples 1 to 38, Comparative Examples 1 to 3, and Reference Examples 1 to 3 will be described.

[0190] <Preparation of gas barrier film> Example 1 The skin layer was made of ethylene-1-butene-propylene random copolymer resin (ethylene content: 2.5 mol%, 1-butene content: 3.5 mol%), and the core layer was made of homopolypropylene resin. These resins were co-extruded and then biaxially stretched to produce a substrate film (substrate layer) with a total thickness of 20 μm. The skin layer was 0.7 μm thick, and the core layer was 19.3 μm thick.

[0191] An acrylic primer solution was applied by gravure coating onto the skin layer of the base material layer, and dried to form an anchor coat layer with a thickness of 0.1 μm. Next, reactive deposition was performed by high-frequency excited ion plating in an oxygen atmosphere under reduced pressure to deposit a thin film of silicon oxide with a thickness of 30 nm onto the anchor coat layer, forming a deposition layer made of inorganic oxide.

[0192] Tetraethoxysilane (hereinafter referred to as "TEOS"), methanol, and 0.1N hydrochloric acid were mixed in a mass ratio of 45 / 15 / 40 to obtain a TEOS hydrolysis solution. This solution, a 5 mass% aqueous solution of polyvinyl alcohol (hereinafter referred to as "PVA"), and a solution of 1,3,5-tris(3-methoxysilylpropyl)isocyanurate in a water / IPA (isopropyl alcohol) mass ratio of 1 / 1 to obtain a solid content of 5 mass% (R 2 The coating liquid (composition for forming a gas barrier coating layer) was prepared by mixing the solution diluted to a concentration of SiO2 solids (converted value) of TEOS and R of isocyanurate silane. 2The liquid was prepared so that the mass ratio of the Si(OH)3 solid content (converted value) to the PVA solid content was 40 / 5 / 55. This coating liquid was applied onto the deposition layer by gravure coating and then dried at 80°C for 60 seconds to form a gas barrier coating layer with a thickness of 0.3 μm.

[0193] In this manner, a gas barrier film of Example 1 having a laminated structure of gas barrier coating layer / vapor deposition layer / anchor coat layer / skin layer / core layer was obtained.

[0194] Example 2 A gas barrier film was obtained in the same manner as in Example 1, except that an ethylene-propylene random copolymer resin (ethylene content: 5.0 mol %) was used as the material for the skin layer.

[0195] Example 3 A gas barrier film was obtained in the same manner as in Example 1, except that an ethylene-propylene random copolymer resin (ethylene content: 3.2 mol %) was used as the material for the skin layer.

[0196] Example 4 A gas barrier film was obtained in the same manner as in Example 1, except that an ethylene-propylene random copolymer resin (ethylene content: 7.5 mol %) was used as the material for the skin layer.

[0197] Comparative Example 1 A gas barrier film was obtained in the same manner as in Example 1, except that no skin layer was formed and a base film consisting of only a core layer was used.

[0198] Comparative Example 2 A gas barrier film was obtained in the same manner as in Example 1, except that an ethylene-1-butene-propylene random copolymer resin (ethylene content: 5 mol %, 1-butene content: 6 mol %) was used as the material for the skin layer.

[0199] Comparative Example 3 A gas barrier film was obtained in the same manner as in Example 1, except that an ethylene-propylene random copolymer resin (ethylene content: 0.5 mol %) was used as the material for the skin layer.

[0200] <Preparation of packaging film> A 60 μm-thick unstretched polypropylene film was laminated on the gas barrier coating layer side of the gas barrier film prepared in each example by dry lamination using a two-component curing urethane adhesive, thereby obtaining a packaging film.

[0201] Example 5 The material for the first skin layer was ethylene-1-butene-propylene random copolymer resin (ethylene content: 2.5 mol%, 1-butene content: 3.5 mol%), the material for the core layer was homopolypropylene resin, and the material for the second skin layer was ethylene-propylene random copolymer resin (ethylene content: 7.5 mol%). These resins were co-extruded and then biaxially stretched to produce a substrate film (substrate layer) with a total thickness of 20 μm. The thicknesses of the first skin layer and the second skin layer were both 0.7 μm, and the thickness of the core layer was 18.6 μm.

[0202] Next, the respective layers were laminated onto the first skin layer of the base layer using the same operations as in Example 1 to obtain the gas barrier film of Example 5 having a laminate structure of gas barrier coating layer / vapor deposition layer / anchor coat layer / first skin layer / core layer / second skin layer.

[0203] Example 6 A gas barrier film was obtained in the same manner as in Example 5, except that an ethylene-propylene random copolymer resin (ethylene content: 5.6 mol %) was used as the material for the second skin layer.

[0204] Example 7 A gas barrier film was obtained in the same manner as in Example 1, except that a corona treatment was performed on the surface of the core layer opposite to the surface on which the first skin layer was laminated.

[0205] (Reference example 1) A gas barrier film was obtained in the same manner as in Example 6, except that a homopolypropylene resin was used as the material for the second skin layer.

[0206] (Reference example 2) A gas barrier film was obtained in the same manner as in Example 6, except that an ethylene-propylene random copolymer resin (ethylene content: 0.7 mol %) was used as the material for the second skin layer.

[0207] (Reference example 3) A gas barrier film was obtained in the same manner as in Example 6, except that an ethylene-1-butene-1-propylene random copolymer resin (ethylene content: 5 mol%, 1-butene content: 6 mol%) was used as the material for the second skin layer.

[0208] <Preparation of packaging film> A 20 μm-thick stretched polypropylene film was laminated on the gas barrier coating layer side of the gas barrier film prepared in each example by a dry lamination method via a two-component curing urethane adhesive. Also, a 60 μm-thick unstretched polypropylene film was laminated on the base layer side of the gas barrier film by a dry lamination method via a two-component curing urethane adhesive. This resulted in a packaging film.

[0209] Example 8 A gas barrier film was obtained by the same procedure as in Example 1, except that a water-based polyurethane resin (Takelac WPB-341, manufactured by Mitsui Chemicals, Inc.) was applied by gravure coating onto the skin layer of the base material layer and dried to form an anchor coat layer having a thickness of 1.5 μm.

[0210] Example 9 A gas barrier film was obtained in the same manner as in Example 1, except that the thickness of the skin layer was 0.3 μm and the thickness of the core layer was 19.7 μm.

[0211] Example 10 A gas barrier film was obtained in the same manner as in Example 1, except that the thickness of the skin layer was 1.5 μm, the thickness of the core layer was 16.5 μm, and the thickness of the anchor coat layer was 1.1 μm.

[0212] Example 11 A gas barrier film was obtained in the same manner as in Example 1, except that the material of the skin layer was a butene-propylene random copolymer resin (butene content: 2.5 mol%), the thickness of the skin layer was 0.7 μm, and the thickness of the anchor coat layer was 2.1 μm.

[0213] Example 12 A gas barrier film was obtained in the same manner as in Example 1, except that the material of the skin layer was a butene-propylene random copolymer resin (butene content: 1.0 mol%), the thickness of the skin layer was 0.7 μm, and the thickness of the anchor coat layer was 3.1 μm.

[0214] (Example 13) The thickness of the anchor coat layer was set to 4.1 μm, and the coating liquid (composition for forming a gas barrier coating layer) was made of TEOS SiO2 solids (converted value) and isocyanurate silane R 2 A gas barrier film was obtained in the same manner as in Example 1, except that the mass ratio of the Si(OH)3 solid content (converted value) to the PVA solid content was adjusted to 45 / 10 / 45.

[0215] Example 14 The thickness of the anchor coat layer was set to 5.1 μm, and the coating liquid (composition for forming a gas barrier coating layer) was made of TEOS SiO2 solids (converted value) and isocyanurate silane R 2 A gas barrier film was obtained in the same manner as in Example 1, except that the mass ratio of the Si(OH)3 solid content (converted value) to the PVA solid content was adjusted to 45 / 7 / 48.

[0216] <Preparation of packaging film> A 60 μm-thick unstretched polypropylene film was laminated on the gas barrier coating layer side of the gas barrier film prepared in each example by dry lamination using a two-component curing urethane adhesive, thereby obtaining a packaging film.

[0217] <Evaluation> (Sample preparation for nanoindentation measurement) The front and back surfaces of the gas barrier film produced in each example were each subjected to a corona treatment at 0.20 kW (equipment: Corona treatment machine CT-0212 manufactured by Kasuga Electric Co., Ltd.), and then the film was cut into a wedge shape with a base of 1.0 mm and a height of 5.0 mm using a razor.

[0218] The cut film was embedded in a photocurable resin and cured with a halogen lamp KTX-100R (Kenko Tokina Co., Ltd.) using the photocurable resin D-800 (Toagosei Co., Ltd.).

[0219] The photocured film embedding resin was fixed with an insert for AFM sample holder, and the cross-section of the film was cut with a glass knife at room temperature (25°C). Then, the final cross-section was cut with a diamond knife at room temperature with a cutting speed of 1.0 mm / s and a cutting layer thickness of 100 nm, and the cutting was completed when a mirror surface was obtained. An ultramicrotome (Leica EM UC7) and a cryosystem (Leica EM FC7) were used as the cross-section cutting device. The cutting direction of the knife was parallel to the layer interface.

[0220] (Nanoindentation measurement) The measurement device used was a Hysitron TI-Premier (product name) manufactured by Bruker Japan, and the indenter used was a Berkovich-type diamond indenter manufactured by Bruker Japan.

[0221] The nanoindentation measurement was performed in displacement control mode by indenting to a depth of 30 nm at a indentation speed of 30 nm / sec, holding the maximum depth for 1 sec, and then unloading at a speed of 30 nm / sec.

[0222] The measurements were performed by acquiring a cross-sectional shape image of the sample using the shape measurement function of a measuring device that scans the sample surface with an indenter, and then specifying 20 points on the target layer at intervals of 1 μm or more from the shape image.

[0223] In calculating the hardness and the composite elastic modulus, a standard sample of fused quartz was tested in advance to calibrate the relationship between the contact depth and the contact projected area of ​​the indenter and the sample. After that, the unloading curve in the 60-95% range of the maximum load at the time of unloading was analyzed by the Oliver-Pharr method, and the hardness and the composite elastic modulus were calculated.

[0224] (retort processing) The packaging films produced in each example were used to produce packaging bags with four sealed sides. The packaging bags were filled with water as the content. Then, they were subjected to retort sterilization at 130°C for 30 minutes.

[0225] (Oxygen permeability measurement) The oxygen permeability of the packaging film after retort treatment was measured. The measurement was performed using an oxygen permeability measuring device (Modern Control, OXTRAN 2 / 20) at a temperature of 30°C and a relative humidity of 70%. The measurement method complies with JIS K-7126, Method B (constant pressure method) and ASTM D3985-81, and the measurement value is in units of [cm 3 (STP) / m 2 The time is expressed as [day·atm].

[0226] (Laminate strength measurement) The laminate strength between the gas barrier film and the unstretched polypropylene film was measured for the packaging film after the retort treatment. The measurement was performed in accordance with JIS K6854, with a test width of 15 mm, a peel speed of 300 mm / min, and a peel angle of 180 degrees. The measured value was expressed in units of [N / 15 mm]. In Examples 1 to 4 and Comparative Examples 1 to 3, the laminate strength between the first skin layer and the unstretched polypropylene film was measured. In Examples 5 to 7 and Reference Examples 1 to 3, the laminate strength between the second skin layer and the unstretched polypropylene film was measured.

[0227] The conditions and evaluation results of each example are shown in Tables 1 to 6. In each table, ethylene-1-butene-propylene random copolymer resin is represented as "EBP", ethylene-propylene random copolymer resin is represented as "EP", butene-propylene random copolymer resin is represented as "BP", homopolypropylene resin is represented as "HPP", acrylic primer solution is represented as "acrylic", water-based polyurethane resin is represented as "urethane", silicon oxide is represented as "SiOx", aluminum oxide is represented as "AlOx", and isocyanurate silane is represented as "SC". When the core layer is subjected to a corona treatment, it is represented as "HPP (corona treatment)".

[0228] As is clear from the results shown in Tables 1 to 6, it was confirmed that the packaging films using the gas barrier films of the examples were able to keep oxygen permeability low even after heat sterilization treatment, and also had excellent laminate strength between each layer.

[0229] As is clear from the results shown in Tables 3 and 4, it was confirmed that providing a second skin layer on the core layer or subjecting it to corona treatment has the effect of increasing the laminate strength between the base layer and the layer adjacent to it.

[0230] [Table 1]

[0231] [Table 2]

[0232] [Table 3]

[0233] [Table 4]

[0234] [Table 5]

[0235] [Table 6]

[0236] Example 15 A 60 μm-thick unstretched polypropylene film was laminated to the gas barrier coating layer side of the gas barrier film produced in Example 1 via a two-component curing urethane adhesive (a) by dry lamination to obtain a packaging film.

[0237] (Examples 16 to 20) Packaging films of Examples 16 to 20 were obtained in the same manner as in Example 15, except that the two-component curing urethane adhesives (b) to (f) were used instead of the adhesive (a).

[0238] Example 21 A 60 μm-thick unstretched polypropylene film was laminated to the gas barrier coating layer side of the gas barrier film produced in Example 2 by dry lamination using a two-component curing urethane adhesive (a) to obtain a packaging film.

[0239] (Examples 22 to 26) Packaging films of Examples 24 to 28 were obtained in the same manner as in Example 21, except that the two-component curing urethane adhesives (b) to (f) were used instead of the adhesive (a).

[0240] Example 27 A 60 μm-thick unstretched polypropylene film was laminated to the gas barrier coating layer side of the gas barrier film produced in Example 3 via a two-component curing urethane adhesive (a) by dry lamination to obtain a packaging film.

[0241] (Examples 28 to 32) Packaging films of Examples 28 to 32 were obtained in the same manner as in Example 27, except that the two-component curing urethane adhesives (b) to (f) were used instead of the adhesive (a).

[0242] (Example 33) A 60 μm-thick unstretched polypropylene film was laminated to the gas barrier coating layer side of the gas barrier film produced in Example 4 by dry lamination using a two-component curing urethane adhesive (a) to obtain a packaging film.

[0243] (Examples 34 to 38) Packaging films of Examples 34 to 48 were obtained in the same manner as in Example 33, except that the two-component curing urethane adhesives (b) to (f) were used instead of the adhesive (a).

[0244] <Evaluation> (retort processing) The packaging films produced in each example were used to produce packaging bags with four sealed sides. The packaging bags were filled with water as the content. Then, they were subjected to retort sterilization at 130°C for 60 minutes.

[0245] (Adhesive layer hardness measurement) In each of Examples 15 to 38, a packaging film that was a part of the packaging bag after retort treatment was cut out. An epoxy adhesive (manufactured by Konishi Co., Ltd., product name: Bond E Set) was applied onto the base layer of the cut-out packaging film. The packaging film was then attached to a glass plate via the epoxy adhesive to form a sample having a packaging film smoothly fixed to the glass plate.

[0246] After the epoxy adhesive hardened, the sample was placed on an oblique cutting device (manufactured by Daipla Wintes Co., Ltd., product name: SAICAS DN-GS). Next, a diamond cutting blade with a V-shaped tip was attached to the oblique cutting device, and side cut lines were applied to the surface of the sealant layer at 1 mm intervals. Next, a diamond knife with a blade width of 1 mm, a rake angle of 20 degrees, and a clearance angle of 10 degrees was contacted with the surface of the sealant layer with a load of 0.05 N, and then the sealant layer was obliquely cut at a horizontal speed of 50 μm / s and a vertical speed of 1 μm / s. At this time, first, after the cutting depth reached 55 μm, it was cut horizontally for 10 mm. Next, finish cutting was performed at a cutting depth of 1 μm at a horizontal speed of 50 μm / s and a vertical speed of 1 μm / s. The exposed surface after cutting was observed, and the number of finish cuts was added as necessary until the desired exposed surface of the adhesive layer was obtained. As described above, the preliminary preparation (i.e., preparation for exposing the adhesive layer) for measuring the hardness of the adhesive layer after retort treatment by the nanoindentation method was completed.

[0247] Next, a Hysitron TI-Premier (trade name) manufactured by Bruker Japan Co., Ltd. was used as a device for measuring the hardness of the adhesive layer by the nanoindentation method. A Berkovich-type diamond indenter manufactured by Bruker Japan Co., Ltd. was used as the indenter. Then, after placing the sample with the exposed adhesive layer on the above device, the indenter was pressed into the sample at room temperature (25°C) with a pressing speed of 100 nm / sec and a test depth of 125 nm in the displacement control mode. Then, after holding at the maximum displacement for 2 seconds, the load was removed at a speed of 50 nm / sec. The surface load was set to 1 μN, and surface correction was performed using TriboScan software. The measurement points were measured by observing the optical microscope image, and 30 points were specified at intervals of 30 μm or more on the sample surface, that is, the exposed surface of the adhesive layer (a point 1 / 4 away from the sealant side when the distance between the sealant layer and the base layer on the exposed surface is divided into 4 equal parts) and measurement was performed by the nanoindentation method. The hardness of the adhesive layer was calculated by first testing a standard sample of fused quartz in advance and calibrating the relationship between the contact depth and the contact projection area between the indenter and the sample.Then, the unloading curve in the 20-95% range of the maximum load at the time of unloading was analyzed using the Oliver-Pharr method to calculate the hardness.

[0248] (Oxygen permeability) The oxygen transmission rate of the packaging film after the retort treatment was measured in the same manner as described above.

[0249] (Laminate strength measurement) The laminate strength between the gas barrier film and the unstretched polypropylene film after the retort treatment was measured in the same manner as described above.

[0250] The conditions and evaluation results of each example are shown in Table 7. As is clear from the results shown in Table 7, the harder the adhesive layer is, the higher the oxygen permeability measurement result is. In addition, it was confirmed that the laminate strength was excellent, similar to Examples 1 to 14.

[0251] [Table 7]

[0252] Next, Examples 45 to 80 and Comparative Examples 5 to 24 will be described.

[0253] <Base material, outermost layer and sealant layer> A biaxially oriented polypropylene (OPP) film (manufactured by Mitsui Chemicals Tocello Co., Ltd., product name: ME-1, thickness: 20 μm) was prepared as the substrate and outermost layer. A non-oriented polypropylene (CPP) film (manufactured by Toray Advanced Film Co., Ltd., product name: Torayfan ZK93KM, thickness: 60 μm) was prepared as the sealant layer.

[0254] <Preparation of Adhesion Layer-Forming Composition> A mixed solution was produced by mixing and stirring γ-isocyanatepropyltrimethoxysilane:acrylic polyol at a ratio of 1:5. Next, tolylene diisocyanate (TDI) was added to the mixed solution so that the number of NCO groups of tolylene diisocyanate was equal to the number of OH groups of the acrylic polyol. Then, the mixed solution was diluted with ethyl acetate to 2% by mass. This prepared a composition for forming an adhesion layer (anchor coating agent).

[0255] <Preparation of coating solution α for barrier coat> The following liquids A, B, and C were prepared in amounts of 10 g each and mixed to prepare coating liquid α.

[0256] Liquid A: A hydrolysis solution with a solid content of 5 mass% (SiO2 equivalent) obtained by adding 72.1 g of 0.1N hydrochloric acid to 17.9 g of tetraethoxysilane (Si(OC2H5)4) and 10 g of methanol and stirring for 30 minutes.

[0257] Liquid B: 5% by mass solution of polyvinyl alcohol in water / methanol (mass ratio of water:methanol is 95:5).

[0258] Liquid C: A hydrolysis solution in which 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate was diluted with a mixture of water and isopropyl alcohol (water:isopropyl alcohol mass ratio 1:1) to a solid content of 5 mass%.

[0259] <Preparation of coating solution β for barrier coat> First, TEOS, methanol, and 0.1N hydrochloric acid were mixed in a mass ratio of 45 / 15 / 40 to obtain a TEOS hydrolysis solution. This solution, a 5 mass% aqueous solution of polyvinyl alcohol (hereinafter referred to as "PVA"), and a silane coupling agent, 1,3,5-tris(3-methoxysilylpropyl)isocyanurate, in a water / IPA (isopropyl alcohol) = 1 / 1 solution, were mixed to obtain a solid content of 5 mass% (R 2 The coating solution β was prepared by mixing the three solutions, TEOS (SiO2 solids equivalent) and isocyanurate silane (R). 2 The solution was prepared so that the mass ratio of Si(OH)3 solids (converted value) to PVA solids was 40 / 5 / 55.

[0260] <Preparation of coating solution γ for barrier coat> A coating liquid γ was prepared by mixing 40 to 75 mass % of an "aqueous polyurethane resin", 10 to 40 mass % of a "water-soluble polymer", and 5 to 20 mass % of a "silane coupling agent".

[0261] Aqueous polyurethane resin: an aqueous dispersion of an aqueous polyurethane resin containing an acid group-containing polyurethane resin and a polyamine compound, an aqueous polyurethane dispersion "Takelac (registered trademark) WPB-341" manufactured by Mitsui Chemicals, Inc., with a solid content of 30%.

[0262] Water-soluble polymer: polyvinyl alcohol with a saponification degree of 98 to 99% and a polymerization degree of 500 (product name: Poval PVA-105, manufactured by Kuraray Co., Ltd.).

[0263] Silane coupling agent: 3-glycidoxypropyltriethoxysilane (product name: KBE-403, manufactured by Shin-Etsu Chemical Co., Ltd.).

[0264] (Example 45) The adhesive layer forming composition was applied to the substrate using a bar coater, and the adhesive layer forming composition was dried at 50° C. This resulted in the formation of an adhesive layer (anchor coat layer) having a thickness of 0.2 μm. Next, a transparent deposition layer (silica deposition layer) made of silicon oxide having a thickness of 40 nm was formed using a vacuum deposition apparatus using an electron beam heating method.

[0265] Next, the coating liquid α was applied onto the deposition layer using a bar coater, and the coating liquid α was dried at 60° C. for 1 minute. As a result, a barrier coat having a thickness of 300 nm was formed on the deposition layer. In this manner, a barrier layer having a substrate, an adhesion layer, a deposition layer, and a barrier coat was formed.

[0266] Next, a two-liquid curing urethane adhesive (a) was applied onto the barrier coat of the barrier layer to form an adhesive layer with a thickness of 3 μm. Next, a sealant layer was laminated via the adhesive layer by dry lamination. This produced a laminate (gas barrier laminate) having a laminated structure of the substrate, adhesion layer, deposition layer, barrier coat, adhesive layer, and sealant layer. The polypropylene content in the obtained laminate was 90% by mass or more.

[0267] (Examples 46 to 50) Laminates of Examples 46 to 50 were produced in the same manner as in Example 1, except that two-component curing urethane adhesives (b) to (f) were used instead of the adhesive (a).

[0268] (Examples 51 to 56) Laminates of Examples 51 to 56 were produced in the same manner as in Examples 45 to 50, except that coating liquid β was used instead of coating liquid α.

[0269] (Examples 57 to 62) Laminates of Examples 57 to 62 were produced in the same manner as in Examples 45 to 50, except that coating liquid γ was used instead of coating liquid α.

[0270] (Example 63) After forming a barrier layer in the same manner as in Example 45, a two-component curing urethane adhesive (a) was applied onto the barrier coat of the barrier layer to form an adhesive layer having a thickness of 3 μm. Next, the outermost layer was laminated via the adhesive layer by a dry lamination method. Next, a two-component curing urethane adhesive (a) was applied onto the substrate of the barrier layer to form an adhesive layer having a thickness of 3 μm. Next, a sealant layer was laminated via the adhesive layer by a dry lamination method. In this way, a laminate (gas barrier laminate) having a laminated structure of the outermost layer, the second adhesive layer, the barrier coat, the deposition layer, the adhesion layer, the substrate, the adhesive layer, and the sealant layer was produced. The polypropylene content in the obtained laminate was 90% by mass or more.

[0271] (Examples 64 to 68) Laminates of Examples 64 to 68 were produced in the same manner as in Example 63, except that two-component curing urethane adhesives (b) to (f) were used instead of the adhesive (a).

[0272] (Examples 69 to 74) Laminates of Examples 69 to 74 were produced in the same manner as in Examples 63 to 68, except that coating liquid β was used instead of coating liquid α.

[0273] (Examples 75 to 80) The laminates of Examples 75 to 80 were produced in the same manner as in Examples 63 to 68, except that the coating liquid γ was used instead of the coating liquid α.

[0274] (Comparative Examples 5 to 7) Laminates of Comparative Examples 5 to 7 were produced in the same manner as in Example 45, except that adhesives (g) to (i) were used instead of adhesive (a).

[0275] (Comparative Examples 8 to 10) Laminates of Comparative Examples 8 to 10 were produced in the same manner as in Example 51, except that adhesives (g) to (i) were used instead of adhesive (a).

[0276] (Comparative Examples 11 to 13) Laminates of Comparative Examples 11 to 13 were produced in the same manner as in Example 57, except that adhesives (g) to (i) were used instead of the adhesive (a).

[0277] (Comparative Examples 14 to 16) Laminates of Comparative Examples 14 to 16 were produced respectively in the same manner as in Example 63, except that adhesives (g) to (i) were used instead of adhesive (a).

[0278] (Comparative Examples 17 to 19) Laminates of Comparative Examples 17 to 19 were produced in the same manner as in Example 69, except that adhesives (g) to (i) were used instead of the adhesive (a).

[0279] (Comparative Examples 20 to 22) Laminates of Comparative Examples 20 to 22 were produced in the same manner as in Example 75, except that adhesives (g) to (i) were used instead of the adhesive (a).

[0280] (Comparative Example 23) A laminate of Comparative Example 19 was produced in the same manner as in Example 45, except that a PET film (thickness: 20 μm) was used as the substrate instead of the OPP film.

[0281] Comparative Example 24 A laminate of Comparative Example 20 was produced in the same manner as in Comparative Example 5, except that a PET film (thickness: 20 μm) was used as the substrate instead of the OPP film.

[0282] <Method for measuring the thermal shrinkage rate of substrate> The heat shrinkage of the substrate included in the barrier layer was measured according to the following procedure. The measurement results of the heat shrinkage of the substrate in Examples 45 to 50 and Comparative Examples 5 to 7 are shown in Table 8 below. The measurement results of the heat shrinkage of the substrate in Examples 51 to 56 and Comparative Examples 8 to 10 are shown in Table 9 below. The measurement results of the heat shrinkage of the substrate in Examples 57 to 62 and Comparative Examples 11 to 13 are shown in Table 10 below. The measurement results of the heat shrinkage of the substrate in Examples 63 to 68 and Comparative Examples 14 to 16 are shown in Table 11 below. The measurement results of the heat shrinkage of the substrate in Examples 69 to 74 and Comparative Examples 17 to 19 are shown in Table 12 below. The measurement results of the heat shrinkage of the substrate in Examples 75 to 80 and Comparative Examples 20 to 22 are shown in Table 13 below. The measurement results of the heat shrinkage of the substrate in Comparative Examples 23 and 24 are shown in Table 14 below.

[0283] As shown in FIG. 8(a), the base material to be measured was cut into a size of 200 mm×200 mm to prepare a measurement sample 500. (b) As shown in FIG. 8, two straight lines L1 and L2, each having a length of 120 mm or more and parallel to the TD direction of the measurement sample 500, were written with an interval of 100 mm. (c) As shown in FIG. 8, two straight lines L3 and L4, each having a length of 120 mm or more and parallel to the MD direction of the measurement sample 500, were drawn with an interval of 100 mm. (d) As shown in Fig. 8, seven graduations N1 to N7 were written at 20 mm intervals on the line L1. Graduations were written similarly on the lines L2 to L4. At this time, the graduations of the lines L1 and L2 were aligned so that when the graduations N1 to N7 of the line L1 and the graduations N1 to N7 of the line L2 were connected by straight lines, the lines were parallel to the MD direction. In addition, the graduations of the lines L3 and L4 were aligned so that when the graduations N1 to N7 of the line L3 and the graduations N1 to N7 of the line L4 were connected by straight lines, the lines were parallel to the TD direction. (e) The measurement sample 500 placed on a Teflon (registered trademark) sheet was placed on a glass plate in an oven heated to a predetermined temperature (150°C or 160°C) and heated for 15 minutes. After heating, the measurement sample 500 was removed from the oven and left at room temperature (25°C) for 30 minutes. (f) The linear distance between the scale N1 (intersection of L1 and N1) of the straight line L1 and the scale N1 (intersection of L2 and N1) of the straight line L2 was measured as the MD length before and after heating, and the MD heat shrinkage was calculated by the following formula (1). Similarly, the MD heat shrinkage was calculated at each of the positions of the scales N1 to N7, and the average value of these was determined as the MD heat shrinkage of the measurement sample 500. MD heat shrinkage rate (%) = (MD length before heating - MD length after heating) / MD length before heating × 100 ... (1)

[0284] <Retort processing> Using the laminates produced in each of the Examples and Comparative Examples, packaging bags with four sealed sides were produced. The packaging bags were filled with water as the content. Then, retort sterilization was performed at 130°C for 60 minutes.

[0285] <Adhesive layer hardness measurement> In each of Examples 45 to 62 and Comparative Examples 5 to 13, a laminate was cut out as a part of a packaging bag after retort treatment. An epoxy adhesive (manufactured by Konishi Co., Ltd., product name: Bond E Set) was applied onto the base material of the cut-out laminate. The laminate was then attached to a glass plate via the epoxy adhesive to form a sample having a laminate smoothly fixed to the glass plate. In each of Examples 63 to 80 and Comparative Examples 14 to 22, an epoxy adhesive (manufactured by Konishi Co., Ltd., product name: Bond E Set) was applied onto the outermost layer of the laminate after retort treatment to form a sample.

[0286] After the epoxy adhesive hardened, the sample was placed on an oblique cutting device (manufactured by Daipla Wintes Co., Ltd., product name: SAICAS DN-GS). Next, a diamond cutting blade with a V-shaped tip was attached to the oblique cutting device, and side cut lines were applied to the surface of the sealant layer at 1 mm intervals. Next, a diamond knife with a blade width of 1 mm, a rake angle of 20 degrees, and a clearance angle of 10 degrees was contacted with the surface of the sealant layer with a load of 0.05 N, and then the sealant layer was obliquely cut at a horizontal speed of 50 μm / s and a vertical speed of 1 μm / s. At this time, first, after the cutting depth reached 55 μm, it was cut horizontally for 10 mm. Next, finish cutting was performed at a cutting depth of 1 μm at a horizontal speed of 50 μm / s and a vertical speed of 1 μm / s. The exposed surface after cutting was observed, and the number of finish cuts was added as necessary until the desired exposed surface of the adhesive layer was obtained. As described above, the preliminary preparation (i.e., preparation for exposing the adhesive layer) for measuring the hardness of the adhesive layer after retort treatment by the nanoindentation method was completed.

[0287] Next, a Hysitron TI-Premier (trade name) manufactured by Bruker Japan Co., Ltd. was used as a device for measuring the hardness of the adhesive layer by the nanoindentation method. A Berkovich-type diamond indenter manufactured by Bruker Japan Co., Ltd. was used as the indenter. Then, after placing the sample with the exposed adhesive layer on the above device, the indenter was pressed into the sample at room temperature (25°C) with a pressing speed of 100 nm / sec and a test depth of 125 nm in the displacement control mode. Then, after holding at the maximum displacement for 2 seconds, the load was removed at a speed of 50 nm / sec. The surface load was set to 1 μN, and surface correction was performed using TriboScan software. The measurement points were measured by observing the optical microscope image, and 30 points were specified at intervals of 30 μm or more on the sample surface, that is, the exposed surface of the adhesive layer (a point 1 / 4 away from the sealant side when the distance between the sealant layer and the base layer on the exposed surface is divided into 4 equal parts) and measurement was performed by the nanoindentation method. The method of calculating the hardness of the adhesive layer is to first test fused quartz as a standard sample in advance and calibrate the relationship between the contact depth and the contact projection area of ​​the indenter and the sample.Then, the unloading curve in the 20 to 95% region of the maximum load at the time of unloading is analyzed by the Oliver-Pharr method to calculate the hardness.The measurement results of the hardness of the adhesive layer in each of Examples 45 to 80 and Comparative Examples 5 to 24 are shown in the following Tables 8 to 14.

[0288] (Oxygen permeability measurement) The oxygen transmission rate (OTR) of the laminate after retort treatment was measured. The measurement was performed using an oxygen transmission rate measuring device (Modern Control, OXTRAN 2 / 20) at a temperature of 30°C and a relative humidity of 70%. The OTR measurement method complies with JIS K-7126, Method B (constant pressure method), and ASTM D3985-81, and the measured OTR value is expressed in units of [cc / m 2 The OTR was expressed in units of [day·atm]. The measurement results of the OTR for each of Examples 45 to 80 and Comparative Examples 5 to 24 are shown in the following Tables 8 to 14.

[0289] [Table 8]

[0290] [Table 9]

[0291] [Table 10]

[0292] [Table 11]

[0293] [Table 12]

[0294] [Table 13]

[0295] [Table 14]

[0296] In all of Tables 8 to 14, the higher the hardness of the adhesive layer, the higher the measurement result of the oxygen permeability. However, the absolute value of the oxygen permeability varies greatly depending on whether the thermal shrinkage rate of the substrate is 1% or more. Specifically, when a substrate with a thermal shrinkage rate of 1% or more is used, as shown in Tables 8 to 13, the oxygen permeability when the hardness of the adhesive layer is 0.9 MPa or more is higher than the oxygen permeability when the hardness of the adhesive is 0.8 MPa. In addition, when the hardness of the adhesive layer is 0.9 MPa or more, the oxygen permeability is at least 3.5 or more. In contrast, when a substrate with a thermal shrinkage rate of less than 1% is used, as shown in Table 7, the difference between the oxygen permeability when the hardness of the adhesive layer is 0.9 MPa or more and the oxygen permeability when the hardness of the adhesive is 0.8 MPa can be said to be within the margin of error.

[0297] In each of Tables 8 to 10 and Tables 11 to 13, the oxygen permeability of the examples and comparative examples using coating liquid β or coating liquid γ is lower than that of the examples and comparative examples using coating liquid α. Also, the oxygen permeability of the examples and comparative examples having an outermost layer is lower than that of the examples and comparative examples not having an outermost layer. [Explanation of symbols]

[0298] DESCRIPTION OF THE PREFERRED EMBODIMENTS 1...substrate layer, 2, 43...vapor deposition layer, 3...gas barrier coating layer, 10a, 10b...gas barrier film, 11...first skin layer, 12...core layer, 13...second skin layer, 20, 30...packaging film, 22...outer film (outermost layer), 23, 50...sealant layer, 24, 60...adhesive layer, 25, 60A...second adhesive layer, 35, 35A...laminate (packaging film), 40...barrier layer (gas barrier film), 41...substrate (substrate layer), 44...barrier coat (gas barrier coating layer), 70...outermost layer, 100...packaging bag.

Claims

1. A gas barrier film including, in this order, a substrate layer containing a polypropylene-based resin, a vapor deposition layer containing an inorganic oxide, and a gas barrier coating layer; a sealant layer overlying the gas barrier coating layer; A packaging film comprising an adhesive layer that bonds the gas barrier coating layer and the sealant layer, The substrate layer comprises a first skin layer and a core layer which is a biaxially oriented polypropylene film, and the deposition layer is formed on the first skin layer side, the hardness of the first skin layer is 0.02 to 0.15 GPa, the hardness of the core layer is 0.07 GPa or more and 0.2 GPa or less, and the composite elastic modulus of the core layer is 2.0 GPa or more, as measured by a nanoindentation method, and the hardness of the core layer is greater than the hardness of the first skin layer; A packaging film, wherein after the packaging film is subjected to a retort treatment, the hardness of the adhesive layer measured by a nanoindentation method is 0.1 MPa or more and less than 0.9 MPa.

2. The packaging film of claim 1 , wherein the first skin layer comprises a propylene-α-olefin copolymer.

3. 2. The packaging film of claim 1, wherein the ratio of the thickness of the first skin layer to the thickness of the core layer is from 1 / 100 to 1 / 5.

4. 2. The packaging film of claim 1, wherein the first skin layer has a composite modulus of elasticity of 1.2 to 2.5 GPa as measured by nanoindentation.

5. The packaging film of claim 1 , wherein the inorganic oxide comprises at least one of aluminum oxide and silicon oxide.

6. 2. The packaging film according to claim 1, wherein the gas barrier coating layer is made of a cured product of a composition containing a water-soluble polymer having a hydroxyl group and at least one member selected from the group consisting of a metal alkoxide, a silane coupling agent, and a hydrolyzate thereof.

7. The packaging film of claim 1 , further comprising an anchor coat layer between the substrate layer and the deposition layer.

8. The packaging film of claim 1 , wherein the substrate layer comprises, in order, the first skin layer, the core layer, and a second skin layer.

9. The packaging film of claim 8, wherein the second skin layer comprises a propylene-α-olefin copolymer.

10. The packaging film according to claim 9, wherein the hardness of the second skin layer is 0.02 to 0.15 GPa as measured by a nanoindentation method.

11. A packaging bag made from the packaging film according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Multi-layer polypropylene film

    JP1988290743A

  • Polypropylene based film

    JP1988291929A

  • Film of barrier properties and packaging material using the film

    JP1997290477A

  • Transparent barrier film

    JP2000233476A

  • Gas barrier laminate

    JP2006159801A